Exterior material for power storage device, method for manufacturing the same, and power storage device
By using a multi-layer film structure composed of a base layer, a barrier layer and a hot melt resin layer in the battery case material, the problem of easy compression of the hot melt resin layer in the prior art under high temperature and high pressure conditions is solved, and better insulation performance and overall performance of the battery case are achieved.
Patent Information
- Application Number
- JP2025004202
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2018-10-24
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2039-10-24
AI Technical Summary
The existing battery housing materials tend to cause compression of the hot melt resin layer under high temperature and high pressure conditions, resulting in a degradation of insulation performance.
A multi-layer film structure consisting of a base layer, a barrier layer and a hot melt resin layer is adopted, wherein the logarithmic absorption rate of the first layer of the hot melt resin layer does not exceed 0.20 at 140°C to avoid compression during the hot melt process.
Effectively prevent the compression of the hot melt resin layer during the hot melting process, improve the insulation performance of the shell material, and enhance the overall performance of the battery shell.
Smart Images

Figure 2025063165000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an exterior material for an electricity storage device, a manufacturing method thereof, and an electricity storage device. [Background technology]
[0002] Conventionally, various types of electricity storage devices have been developed, and in all electricity storage devices, exterior materials are essential components for sealing electricity storage device elements such as electrodes, electrolytes, etc. Conventionally, metallic exterior materials have been widely used as exterior materials for electricity storage devices.
[0003] Meanwhile, in recent years, various shapes as well as thinner and lighter weight are required for electricity storage devices along with the increasing performance of electric vehicles, hybrid electric vehicles, personal computers, cameras, mobile phones, etc. However, the metallic exterior materials for electricity storage devices that have been widely used in the past have the drawbacks of being difficult to keep up with the diversification of shapes and also having limitations in terms of weight reduction.
[0004] In recent years, a film-like laminate in which a base layer, a barrier layer, and a heat-sealable resin layer are laminated in this order has been proposed as an exterior material for an electricity storage device that can be easily processed into a variety of shapes and can be made thinner and lighter (see, for example, Patent Document 1).
[0005] In such an exterior material for an electricity storage device, a recess is generally formed by cold forming, and electricity storage device elements such as electrodes and an electrolyte are placed in the space formed by the recess, and the heat-sealable resin layer is then heat-sealed to obtain an electricity storage device in which the electricity storage device elements are housed inside the exterior material for an electricity storage device. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2008-287971 A Summary of the Invention [Problem to be solved by the invention]
[0007] When sealing an electricity storage device element, a heat-sealable resin layer is heat-sealed by applying high temperature and high pressure to the electricity storage device exterior material using a metal plate, etc. However, the inventors of the present disclosure have conducted research and found that applying high temperature and high pressure to the electricity storage device exterior material causes the heat-sealable resin layer located on the surface to be crushed, resulting in a decrease in the insulating properties of the electricity storage device exterior material.
[0008] Under these circumstances, the main object of the present invention is to provide an exterior material for an electricity storage device that is composed of a laminate having at least a base material layer, a barrier layer, and a heat-sealable resin layer in this order, and that is capable of effectively suppressing crushing when the heat-sealable resin layer is heat-sealed. [Means for solving the problem]
[0009] The inventors of the present disclosure conducted intensive studies to solve the above-mentioned problems. As a result, they found that an exterior material for an electricity storage device, which is composed of a laminate including at least a base layer, a barrier layer, and a heat-sealable resin layer in this order, the heat-sealable resin layer being composed of a single layer or multiple layers, and in which a first heat-sealable resin layer constituting a surface of the laminate among the heat-sealable resin layers has a logarithmic decrement ΔE of 0.20 or less at 140°C in a rigid pendulum measurement, is effectively suppressed from collapsing when the heat-sealable resin layer is heat-sealed.
[0010] The present disclosure has been completed based on these findings and through further investigations. That is, the present disclosure provides the invention of the following aspects. The laminate includes at least a base layer, a barrier layer, and a thermally adhesive resin layer in this order. The thermally adhesive resin layer is configured as a single layer or multiple layers, An exterior material for an electricity storage device, wherein among the heat-sealable resin layers, a first heat-sealable resin layer constituting a surface of the laminate has a logarithmic decrement ΔE of 0.20 or less at 140°C in a rigid pendulum measurement. Effect of the Invention
[0011] According to the present disclosure, it is possible to provide an exterior material for an electricity storage device that is composed of a laminate having at least a base layer, a barrier layer, and a heat-sealable resin layer in this order, and that effectively suppresses crushing when the heat-sealable resin layer is heat-sealed. By suppressing crushing, for example, improvement in insulation can be expected. Furthermore, according to the present disclosure, it is also possible to provide a manufacturing method for an exterior material for an electricity storage device, and an electricity storage device. [Brief description of the drawings]
[0012] [Figure 1] 1 is a schematic diagram showing an example of a cross-sectional structure of an exterior material for an electricity storage device according to the present disclosure. [Diagram 2] 1 is a schematic diagram showing an example of a cross-sectional structure of an exterior material for an electricity storage device according to the present disclosure. [Diagram 3] 1 is a schematic diagram showing an example of a cross-sectional structure of an exterior material for an electricity storage device according to the present disclosure. [Figure 4] 1 is a schematic diagram showing an example of a cross-sectional structure of an exterior material for an electricity storage device according to the present disclosure. [Diagram 5] 1 is a schematic diagram showing an example of a cross-sectional structure of an exterior material for an electricity storage device according to the present disclosure. [Figure 6] FIG. 1 is a schematic diagram for explaining a method for measuring a logarithmic decrement ΔE by rigid pendulum measurement. [Figure 7] 1 is a photomicrograph (taken at a magnification of 20 times) of a cross section of a heat-sealed portion between heat-sealable resin layers of the exterior material for an electricity storage device obtained in Example 1. [Figure 8] 1 is a photomicrograph (taken at a magnification of 20 times) of a cross section of a heat-sealed portion between heat-sealable resin layers of an exterior material for an electricity storage device obtained in Example 2. [Figure 9]1 is a photomicrograph (taken at a magnification of 20 times) of a cross section of a heat-sealed portion between heat-sealable resin layers of an exterior material for an electricity storage device obtained in Comparative Example 1. [Figure 10] 1 is a photomicrograph (taken at a magnification of 20 times) of a cross section of a heat-sealed portion between heat-sealable resin layers of an exterior material for an electricity storage device obtained in Comparative Example 2. [Figure 11] 4 is a schematic diagram for explaining a protrusion formed inside a heat-sealed portion of a heat-sealable resin layer. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The exterior packaging material for an electricity storage device of the present disclosure is composed of a laminate having at least a base layer, a barrier layer, and a heat-sealable resin layer in this order, the heat-sealable resin layer being composed of a single layer or multiple layers, and among the heat-sealable resin layers, a first heat-sealable resin layer constituting the surface of the laminate is characterized in that the logarithmic decrement ΔE at 140° C. in rigid pendulum measurement is 0.20 or less. According to the exterior packaging material for an electricity storage device of the present disclosure, by having this configuration, crushing when the heat-sealable resin layer is heat-sealed is effectively suppressed.
[0014] The exterior material for an electricity storage device according to the present disclosure will be described in detail below. In this specification, the numerical range indicated by "to" means "not less than" or "not more than." For example, the expression "2 to 15 mm" means 2 mm or more and 15 mm or less.
[0015] 1.Laminated structure of exterior materials for energy storage devices The exterior material 10 for an electric storage device according to the present disclosure is composed of a laminate including at least a base material layer 1, a barrier layer 3, and a heat-sealable resin layer 4 in this order, as shown in, for example, FIG. 1 to FIG. 5. In the exterior material 10 for an electric storage device, the base material layer 1 is the outermost layer, and the heat-sealable resin layer 4 is the inner layer. In the exterior material 10 for an electric storage device according to the present disclosure, the heat-sealable resin layer 4 is composed of a single layer or multiple layers, and among the heat-sealable resin layers 4, the first heat-sealable resin layer 41 constitutes the surface of the laminate. FIG. 1 and FIG. 2 show a laminate structure in which the heat-sealable resin layer 4 is composed of a single layer of the first heat-sealable resin layer 41, and the first heat-sealable resin layer 41 constitutes the surface of the laminate. 3 to 5 show a laminated structure in which the heat-sealable resin layer 4 is composed of a multi-layer (two layers) of a first heat-sealable resin layer 41 and a second heat-sealable resin layer 42, and the first heat-sealable resin layer 41 constitutes the surface of the laminate. As described later, the heat-sealable resin layer 4 may further include other heat-sealable resin layers, such as a third heat-sealable resin layer and a fourth heat-sealable resin layer, on the barrier layer 3 side of the second heat-sealable resin layer 42 in addition to the first heat-sealable resin layer 41 and the second heat-sealable resin layer 42.
[0016] When assembling an electricity storage device using the exterior material 10 for an electricity storage device and an electricity storage device element, the first heat-sealable resin layers 41 of the exterior material 10 for an electricity storage device are placed facing each other, and the electricity storage device element is housed in a space formed by heat-sealing the peripheral portions.
[0017] As shown in Figures 2 to 5, for example, the exterior material 10 for an electricity storage device may have an adhesive layer 2 between the base material layer 1 and the barrier layer 3, if necessary, for the purpose of increasing the adhesion between these layers. Also, as shown in Figures 2, 4 and 5, for example, the exterior material 10 for an electricity storage device may have an adhesive layer 5 between the barrier layer 3 and the heat-sealable resin layer 4, if necessary, for the purpose of increasing the adhesion between these layers. Also, as shown in Figure 5, a surface coating layer 6 or the like may be provided on the outer side of the base material layer 1 (the side opposite to the heat-sealable resin layer 4 side) if necessary.
[0018] The thickness of the laminate constituting the exterior material 10 for an electricity storage device is not particularly limited, but from the viewpoint of cost reduction, improving energy density, etc., it is preferably about 180 μm or less, about 155 μm or less, and from the viewpoint of maintaining the function of the exterior material for an electricity storage device, which is to protect the electricity storage device elements, it is preferably about 35 μm or more, about 45 μm or more, about 60 μm or more, and preferred ranges include, for example, about 35 to 180 μm, about 35 to 155 μm, about 45 to 180 μm, about 45 to 155 μm, about 60 to 180 μm, and about 60 to 155 μm.
[0019] 2. Each layer that forms the exterior material for electricity storage devices [Base material layer 1] In the present disclosure, the substrate layer 1 is a layer provided for the purpose of exhibiting the function as a substrate of the exterior material for an electricity storage device, etc. The substrate layer 1 is located on the outer layer side of the exterior material for an electricity storage device.
[0020] The material forming the base layer 1 is not particularly limited as long as it has the function of a base, that is, at least insulating properties. The base layer 1 can be formed using, for example, a resin, and the resin may contain additives described later.
[0021] When the base layer 1 is made of a resin, the base layer 1 may be, for example, a resin film made of a resin, or may be formed by applying a resin. The resin film may be an unstretched film or a stretched film. Examples of stretched films include uniaxially stretched films and biaxially stretched films, and biaxially stretched films are preferred. Examples of stretching methods for forming biaxially stretched films include sequential biaxial stretching, inflation, and simultaneous biaxial stretching. Examples of methods for applying a resin include roll coating, gravure coating, and extrusion coating.
[0022] Examples of the resin forming the base layer 1 include polyester, polyamide, polyolefin, epoxy resin, acrylic resin, fluororesin, polyurethane, silicone resin, and phenol resin, as well as modified versions of these resins. The resin forming the base layer 1 may be a copolymer of these resins or a modified version of the copolymer. Furthermore, it may be a mixture of these resins.
[0023] Of these, preferred examples of the resin forming the base layer 1 include polyester and polyamide.
[0024] Specific examples of polyesters include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, and copolymerized polyesters. Examples of copolymerized polyesters include copolymerized polyesters in which ethylene terephthalate is the main repeating unit. Specific examples of polyesters include copolymerized polyesters in which ethylene terephthalate is the main repeating unit and is polymerized with ethylene isophthalate (hereinafter abbreviated as polyethylene (terephthalate / isophthalate)), polyethylene (terephthalate / adipate), polyethylene (terephthalate / sodium sulfoisophthalate), polyethylene (terephthalate / sodium isophthalate), polyethylene (terephthalate / phenyl-dicarboxylate), and polyethylene (terephthalate / decane dicarboxylate). These polyesters may be used alone or in combination of two or more.
[0025] Specific examples of polyamides include aliphatic polyamides such as nylon 6, nylon 66, nylon 610, nylon 12, nylon 46, and copolymers of nylon 6 and nylon 66; hexamethylenediamine-isophthalic acid-terephthalic acid copolymer polyamides such as nylon 6I, nylon 6T, nylon 6IT, and nylon 6I6T (I represents isophthalic acid, and T represents terephthalic acid) that contain structural units derived from terephthalic acid and / or isophthalic acid, and polyamides containing aromatic compounds such as polyamide MXD6 (polymetaxylylene adipamide); alicyclic polyamides such as polyamide PACM6 (polybis(4-aminocyclohexyl)methane adipamide); polyamides copolymerized with a lactam component or an isocyanate component such as 4,4'-diphenylmethane diisocyanate; polyesteramide copolymers and polyetheresteramide copolymers that are copolymers of copolymerized polyamides with polyesters or polyalkylene ether glycols; and polyamides such as copolymers of these copolymers. These polyamides may be used alone or in combination of two or more.
[0026] The base layer 1 preferably includes at least one of a polyester film, a polyamide film, and a polyolefin film, preferably includes at least one of a stretched polyester film, a stretched polyamide film, and a stretched polyolefin film, more preferably includes at least one of a stretched polyethylene terephthalate film, a stretched polybutylene terephthalate film, a stretched nylon film, and a stretched polypropylene film, and even more preferably includes at least one of a biaxially oriented polyethylene terephthalate film, a biaxially oriented polybutylene terephthalate film, a biaxially oriented nylon film, and a biaxially oriented polypropylene film.
[0027] The base layer 1 may be a single layer, or may be composed of two or more layers. When the base layer 1 is composed of two or more layers, the base layer 1 may be a laminate in which resin films are laminated with an adhesive or the like, or may be a laminate of resin films in which resins are co-extruded to form two or more layers. In addition, a laminate of resin films in which resins are co-extruded to form two or more layers may be used as the base layer 1 without being stretched, or may be uniaxially or biaxially stretched to form the base layer 1.
[0028] In the base layer 1, specific examples of the laminate of two or more resin films include a laminate of a polyester film and a nylon film, a laminate of two or more nylon films, and a laminate of two or more polyester films, and preferably a laminate of a stretched nylon film and a stretched polyester film, a laminate of two or more stretched nylon films, and a laminate of two or more stretched polyester films. For example, when the base layer 1 is a laminate of two resin films, a laminate of a polyester resin film and a polyester resin film, a laminate of a polyamide resin film and a polyamide resin film, or a laminate of a polyester resin film and a polyamide resin film is preferred, and a laminate of a polyethylene terephthalate film and a polyethylene terephthalate film, a laminate of a nylon film and a nylon film, or a laminate of a polyethylene terephthalate film and a nylon film is more preferred. In addition, when the base layer 1 is a laminate of two or more resin films, it is preferable that the polyester resin film is located in the outermost layer of the base layer 1, because the polyester resin is less likely to discolor when, for example, an electrolyte is attached to the surface.
[0029] When the base layer 1 is a laminate of two or more resin films, the two or more resin films may be laminated via an adhesive. Preferred adhesives include the same adhesives as those exemplified in the adhesive layer 2 described later. The method for laminating two or more resin films is not particularly limited, and known methods can be adopted, such as dry lamination, sandwich lamination, extrusion lamination, and thermal lamination, and preferably dry lamination. When laminating by the dry lamination method, it is preferable to use a polyurethane adhesive as the adhesive. In this case, the thickness of the adhesive is, for example, about 2 to 5 μm. Also, an anchor coat layer may be formed on the resin film and laminated. The anchor coat layer may be the same adhesive as that exemplified in the adhesive layer 2 described later. In this case, the thickness of the anchor coat layer is, for example, about 0.01 to 1.0 μm.
[0030] Furthermore, additives such as lubricants, flame retardants, antiblocking agents, antioxidants, light stabilizers, tackifiers, and antistatic agents may be present on at least one of the surface and the interior of the base layer 1. The additives may be used alone or in combination of two or more.
[0031] In the present disclosure, from the viewpoint of improving the moldability of the exterior material for a power storage device, it is preferable that a lubricant is present on the surface of the base material layer 1. The lubricant is not particularly limited, but is preferably an amide-based lubricant. Specific examples of amide-based lubricants include, for example, saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, methylol amides, saturated fatty acid bisamides, unsaturated fatty acid bisamides, fatty acid ester amides, and aromatic bisamides. Specific examples of saturated fatty acid amides include lauric acid amides, palmitic acid amides, stearic acid amides, behenic acid amides, and hydroxystearic acid amides. Specific examples of unsaturated fatty acid amides include oleic acid amides and erucic acid amides. Specific examples of substituted amides include N-oleyl palmitic acid amides, N-stearyl stearic acid amides, N-stearyl oleic acid amides, N-oleyl stearic acid amides, and N-stearyl erucic acid amides. Specific examples of methylol amides include methylol stearic acid amides. Specific examples of saturated fatty acid bisamides include methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, ethylene bisstearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene hydroxystearic acid amide, N,N'-distearyl adipic acid amide, N,N'-distearyl sebacic acid amide, etc. Specific examples of unsaturated fatty acid bisamides include ethylene bisoleic acid amide, ethylene biserucic acid amide, hexamethylene bisoleic acid amide, N,N'-dioleyl adipic acid amide, N,N'-dioleyl sebacic acid amide, etc. Specific examples of fatty acid ester amides include stearamide ethyl stearate, etc. Specific examples of aromatic bisamides include m-xylylene bisstearic acid amide, m-xylylene bishydroxystearic acid amide, N,N'-distearylisophthalic acid amide, etc. The lubricant may be used alone or in combination of two or more kinds.
[0032] When a lubricant is present on the surface of the base layer 1, the amount of the lubricant is not particularly limited, but is preferably about 3 mg / m 2 More preferably, 4 to 15 mg / m 2 about 5 to 14 mg / m 2 The degree of
[0033] The lubricant present on the surface of the base layer 1 may be a lubricant exuded from the resin constituting the base layer 1, or a lubricant applied to the surface of the base layer 1.
[0034] The thickness of the substrate layer 1 is not particularly limited as long as it functions as a substrate, and may be, for example, about 3 to 50 μm, and preferably about 10 to 35 μm. When the substrate layer 1 is a laminate of two or more resin films, the thickness of each of the resin films constituting each layer is, for example, about 2 to 35 μm, and preferably about 2 to 25 μm.
[0035] [Adhesive layer 2] In the exterior material for an electricity storage device of the present disclosure, the adhesive layer 2 is a layer that is provided between the base layer 1 and the barrier layer 3 as necessary for the purpose of increasing the adhesion between them.
[0036] The adhesive layer 2 is formed of an adhesive capable of bonding the base material layer 1 and the barrier layer 3. The adhesive used to form the adhesive layer 2 is not limited, and may be any of a chemical reaction type, a solvent volatilization type, a hot melt type, a hot pressure type, etc. Also, it may be a two-component curing adhesive (two-component adhesive), a one-component curing adhesive (one-component adhesive), or a resin that does not involve a curing reaction. Also, the adhesive layer 2 may be a single layer or multiple layers.
[0037] Specific examples of adhesive components contained in the adhesive include polyesters such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, and copolymerized polyesters; polyethers; polyurethanes; epoxy resins; phenolic resins; polyamides such as nylon 6, nylon 66, nylon 12, and copolymerized polyamides; polyolefins, cyclic polyolefins, acid-modified polyolefins, and acid-modified cyclic polyolefins; polyvinyl acetate; cellulose; (meth)acrylic resins; polyimides; polycarbonates; amino resins such as urea resins and melamine resins; rubbers such as chloroprene rubber, nitrile rubber, and styrene-butadiene rubber; and silicone resins. These adhesive components may be used alone or in combination of two or more. Among these adhesive components, polyurethane adhesives are preferred. In addition, the adhesive strength of these adhesive component resins can be increased by using an appropriate curing agent in combination. The curing agent is selected from polyisocyanates, multifunctional epoxy resins, oxazoline group-containing polymers, polyamine resins, acid anhydrides, and the like, depending on the functional groups of the adhesive components.
[0038] Examples of polyurethane adhesives include polyurethane adhesives containing a base agent containing a polyol compound and a curing agent containing an isocyanate compound. Preferably, a two-component curing polyurethane adhesive is used in which a polyol such as polyester polyol, polyether polyol, or acrylic polyol is used as a base agent and an aromatic or aliphatic polyisocyanate is used as a curing agent. In addition, it is preferable to use a polyester polyol having a hydroxyl group on the side chain in addition to the terminal hydroxyl group of the repeating unit as the polyol compound. Since the adhesive layer 2 is formed from a polyurethane adhesive, the exterior material for the electricity storage device is given excellent electrolyte resistance, and the base layer 1 is prevented from peeling off even if the electrolyte adheres to the side surface.
[0039] In addition, the adhesive layer 2 is allowed to contain other components as long as they do not impair adhesion, and may contain a colorant, a thermoplastic elastomer, a tackifier, a filler, etc. By containing a colorant in the adhesive layer 2, the exterior material for a power storage device can be colored. As the colorant, known colorants such as pigments and dyes can be used. In addition, only one type of colorant may be used, or two or more types may be mixed and used.
[0040] The type of pigment is not particularly limited as long as it does not impair the adhesiveness of the adhesive layer 2. Examples of organic pigments include azo-based, phthalocyanine-based, quinacridone-based, anthraquinone-based, dioxazine-based, indigothioindigo-based, perinone-perylene-based, isoindolenine-based, and benzimidazolone-based pigments, while examples of inorganic pigments include carbon black-based, titanium oxide-based, cadmium-based, lead-based, chromium oxide-based, and iron-based pigments, and other examples include fine powder of mica, fish scale foil, and the like.
[0041] Among colorants, carbon black is preferred in order to give the exterior material for an electricity storage device a black appearance, for example.
[0042] The average particle size of the pigment is not particularly limited and may be, for example, about 0.05 to 5 μm, and preferably about 0.08 to 2 μm. The average particle size of the pigment is the median size measured by a laser diffraction / scattering type particle size distribution measuring device.
[0043] The content of the pigment in the adhesive layer 2 is not particularly limited as long as the exterior material for an electricity storage device is colored, and is, for example, about 5 to 60 mass %, preferably 10 to 40 mass %.
[0044] The thickness of the adhesive layer 2 is not particularly limited as long as it can bond the base layer 1 and the barrier layer 3, and can be, for example, about 1 μm or more, about 2 μm or more, and about 10 μm or less, about 5 μm or less, and preferred ranges include about 1 to 10 μm, about 1 to 5 μm, about 2 to 10 μm, and about 2 to 5 μm.
[0045] [Colored layer] The colored layer is a layer that is provided between the base material layer 1 and the barrier layer 3 as necessary (not shown). When the adhesive layer 2 is provided, a colored layer may be provided between the base material layer 1 and the adhesive layer 2, or between the adhesive layer 2 and the barrier layer 3. Also, a colored layer may be provided on the outside of the base material layer 1. By providing a colored layer, the exterior material for an electricity storage device can be colored.
[0046] The colored layer can be formed, for example, by applying an ink containing a colorant to the surface of the base layer 1, the surface of the adhesive layer 2, or the surface of the barrier layer 3. As the colorant, known substances such as pigments and dyes can be used. Furthermore, only one type of colorant may be used, or two or more types may be mixed together.
[0047] Specific examples of the colorant contained in the colored layer include the same as those described in the section [Adhesive layer 2].
[0048] [Barrier layer 3] In the packaging material for an electricity storage device, the barrier layer 3 is a layer that at least prevents the penetration of moisture.
[0049] Examples of the barrier layer 3 include metal foils, vapor-deposited films, and resin layers having barrier properties. Examples of the vapor-deposited films include metal vapor-deposited films, inorganic oxide vapor-deposited films, and carbon-containing inorganic oxide vapor-deposited films. Examples of the resin layer include fluorine-containing resins such as polyvinylidene chloride, polymers mainly composed of chlorotrifluoroethylene (CTFE), polymers mainly composed of tetrafluoroethylene (TFE), polymers having fluoroalkyl groups, and polymers mainly composed of fluoroalkyl units, and ethylene-vinyl alcohol copolymers. Examples of the barrier layer 3 include resin films having at least one of these vapor-deposited films and resin layers. The barrier layer 3 may be provided in a plurality of layers. The barrier layer 3 preferably includes a layer made of a metal material. Specific examples of the metal material constituting the barrier layer 3 include aluminum alloys, stainless steel, titanium steel, and steel plates. When used as a metal foil, it is preferable to include at least one of aluminum alloy foil and stainless steel foil.
[0050] From the viewpoint of improving the formability of the exterior material for a power storage device, the aluminum alloy foil is preferably a soft aluminum alloy foil made of, for example, an annealed aluminum alloy, and from the viewpoint of further improving the formability, the aluminum alloy foil is preferably an iron-containing aluminum alloy foil. In the iron-containing aluminum alloy foil (100 mass%), the iron content is preferably 0.1 to 9.0 mass%, more preferably 0.5 to 2.0 mass%. By making the iron content 0.1 mass% or more, an exterior material for a power storage device having better formability can be obtained. By making the iron content 9.0 mass% or less, an exterior material for a power storage device having better flexibility can be obtained. Examples of the soft aluminum alloy foil include aluminum alloy foils having a composition specified in JIS H4160:1994 A8021H-O, JIS H4160:1994 A8079H-O, JIS H4000:2014 A8021P-O, or JIS H4000:2014 A8079P-O. Silicon, magnesium, copper, manganese, etc. may be added as necessary. Softening can be performed by annealing or the like.
[0051] Examples of the stainless steel foil include austenitic, ferritic, austenitic-ferritic, martensitic, and precipitation hardened stainless steel foils. From the viewpoint of providing an exterior material for an electricity storage device having excellent formability, the stainless steel foil is preferably made of austenitic stainless steel.
[0052] Specific examples of the austenitic stainless steel constituting the stainless steel foil include SUS304, SUS301, and SUS316L, and among these, SUS304 is particularly preferred.
[0053] In the case of a metal foil, the thickness of the barrier layer 3 should be such that it at least functions as a barrier layer that prevents moisture from penetrating, and is, for example, about 9 to 200 μm. The thickness of the barrier layer 3 is, for example, preferably about 85 μm or less, more preferably about 50 μm or less, even more preferably about 40 μm or less, and particularly preferably about 35 μm or less, and is preferably about 10 μm or more, even more preferably about 20 μm or more, and more preferably about 25 μm or more, and preferred ranges of the thickness include about 10 to 85 μm, about 10 to 50 μm, about 10 to 40 μm, about 10 to 35 μm, about 20 to 85 μm, about 20 to 50 μm, about 20 to 40 μm, about 20 to 35 μm, about 25 to 85 μm, about 25 to 50 μm, about 25 to 40 μm, and about 25 to 35 μm. When the barrier layer 3 is made of an aluminum alloy foil, the above-mentioned range is particularly preferred. In particular, when the barrier layer 3 is made of a stainless steel foil, the thickness of the stainless steel foil is preferably about 60 μm or less, more preferably about 50 μm or less, even more preferably about 40 μm or less, even more preferably about 30 μm or less, and particularly preferably about 25 μm or less, and is preferably about 10 μm or more, more preferably about 15 μm or more, and preferred thickness ranges include about 10 to 60 μm, about 10 to 50 μm, about 10 to 40 μm, about 10 to 30 μm, about 10 to 25 μm, about 15 to 60 μm, about 15 to 50 μm, about 15 to 40 μm, about 15 to 30 μm, and about 15 to 25 μm.
[0054] In addition, when the barrier layer 3 is a metal foil, it is preferable to provide a corrosion-resistant film at least on the surface opposite to the base layer in order to prevent dissolution and corrosion. The barrier layer 3 may be provided with a corrosion-resistant film on both sides. Here, the corrosion-resistant film refers to a thin film that is provided with corrosion resistance (e.g., acid resistance, alkali resistance, etc.) on the surface of the barrier layer by performing, for example, hydrothermal conversion treatment such as boehmite treatment, chemical conversion treatment, anodizing treatment, plating treatment such as nickel or chromium, or corrosion prevention treatment by applying a coating agent. Specifically, the corrosion-resistant film means a film that improves the acid resistance of the barrier layer (acid-resistant film), a film that improves the alkali resistance of the barrier layer (alkali-resistant film), etc. As a treatment for forming a corrosion-resistant film, one type may be performed, or two or more types may be combined. In addition, not only one layer but also multiple layers may be formed. Furthermore, among these treatments, the hydrothermal conversion treatment and the anodizing treatment are treatments in which the metal foil surface is dissolved by a treatment agent to form a metal compound with excellent corrosion resistance. These treatments may be included in the definition of chemical conversion treatment. In addition, when the barrier layer 3 has a corrosion-resistant coating, the barrier layer 3 includes the corrosion-resistant coating.
[0055] The corrosion-resistant coating prevents delamination between a barrier layer (e.g., an aluminum alloy foil) and a base layer during molding of an exterior material for an electricity storage device, prevents dissolution and corrosion of the barrier layer surface due to hydrogen fluoride produced by a reaction between an electrolyte and moisture, and in particular prevents dissolution and corrosion of aluminum oxide present on the barrier layer surface when the barrier layer is an aluminum alloy foil, and also improves the adhesion (wettability) of the barrier layer surface, thereby preventing delamination between the base layer and the barrier layer during heat sealing and between the base layer and the barrier layer during molding.
[0056] Various corrosion-resistant films formed by chemical conversion treatments are known, and mainly include corrosion-resistant films containing at least one of phosphates, chromates, fluorides, triazine thiol compounds, and rare earth oxides. Examples of chemical conversion treatments using phosphates and chromates include chromate chromate treatment, phosphoric acid chromate treatment, phosphoric acid-chromate treatment, and chromate treatment. Examples of chromium compounds used in these treatments include chromium nitrate, chromium fluoride, chromium sulfate, chromium acetate, chromium oxalate, chromium biphosphate, chromate acetyl acetate, chromium chloride, and potassium chromium sulfate. Examples of phosphorus compounds used in these treatments include sodium phosphate, potassium phosphate, ammonium phosphate, and polyphosphoric acid. Examples of chromate treatments include etching chromate treatment, electrolytic chromate treatment, and coating-type chromate treatment, and coating-type chromate treatment is preferred. In this coating type chromate treatment, at least the inner layer side of the barrier layer (e.g., aluminum alloy foil) is first degreased by a known treatment method such as an alkali immersion method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or an acid activation method, and then the degreased surface is coated with a treatment liquid mainly composed of a metal phosphate such as Cr (chromium) phosphate, Ti (titanium) phosphate, Zr (zirconium) phosphate, or Zn (zinc) phosphate, or a mixture of these metal salts, or a treatment liquid mainly composed of a nonmetallic phosphate and a mixture of these nonmetallic salts, or a treatment liquid composed of a mixture of these with a synthetic resin, or the like, by a known coating method such as a roll coating method, a gravure printing method, or a dipping method, and then dried. As the treatment liquid, various solvents such as water, alcohol-based solvents, hydrocarbon-based solvents, ketone-based solvents, ester-based solvents, and ether-based solvents can be used, and water is preferred. Examples of the resin component used here include polymers such as phenolic resins and acrylic resins, and chromate treatment using an aminated phenol polymer having repeating units represented by the following general formulas (1) to (4). In the aminated phenol polymer, the repeating units represented by the following general formulas (1) to (4) may be contained alone or in any combination of two or more types.The acrylic resin is preferably polyacrylic acid, acrylic acid methacrylic acid ester copolymer, acrylic acid maleic acid copolymer, acrylic acid styrene copolymer, or a derivative thereof such as sodium salt, ammonium salt, or amine salt. In particular, a derivative of polyacrylic acid such as an ammonium salt, sodium salt, or amine salt of polyacrylic acid is preferable. In the present disclosure, polyacrylic acid means a polymer of acrylic acid. The acrylic resin is also preferably a copolymer of acrylic acid and dicarboxylic acid or dicarboxylic acid anhydride, and is also preferably an ammonium salt, sodium salt, or amine salt of a copolymer of acrylic acid and dicarboxylic acid or dicarboxylic acid anhydride. Only one type of acrylic resin may be used, or two or more types may be mixed and used.
[0057] [ka]
[0058] [ka]
[0059] [ka]
[0060] [ka]
[0061] In the general formulas (1) to (4), X represents a hydrogen atom, a hydroxy group, an alkyl group, a hydroxyalkyl group, an allyl group, or a benzyl group. 1 and R 2 In the general formulae (1) to (4), X and R each independently represent a hydroxy group, an alkyl group, or a hydroxyalkyl group. 1 and R 2Examples of the alkyl group represented by the formula (I) include linear or branched alkyl groups having 1 to 4 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, and a tert-butyl group. 1 and R 2 Examples of the hydroxyalkyl group represented by the formula (1) to (4) include linear or branched alkyl groups having 1 to 4 carbon atoms substituted with one hydroxy group, such as a hydroxymethyl group, a 1-hydroxyethyl group, a 2-hydroxyethyl group, a 1-hydroxypropyl group, a 2-hydroxypropyl group, a 3-hydroxypropyl group, a 1-hydroxybutyl group, a 2-hydroxybutyl group, a 3-hydroxybutyl group, and a 4-hydroxybutyl group. 1 and R 2 The alkyl group and the hydroxyalkyl group represented by the following formulae may be the same or different. In the general formulae (1) to (4), X is preferably a hydrogen atom, a hydroxy group, or a hydroxyalkyl group. The number average molecular weight of the aminated phenol polymer having the repeating units represented by the general formulae (1) to (4) is preferably about 500 to 1,000,000, for example, and more preferably about 1,000 to 20,000. The aminated phenol polymer can be prepared, for example, by polycondensing a phenol compound or a naphthol compound with formaldehyde to produce a polymer consisting of the repeating units represented by the above general formula (1) or (3), and then polycondensing the polymer with formaldehyde and an amine (R 1 R 2 NH) to the functional group (-CH 2 NR 1 R 2 The aminated phenol polymers can be used alone or in combination of two or more.
[0062] Another example of the corrosion-resistant film is a thin film formed by a coating-type corrosion prevention treatment in which a coating agent containing at least one selected from the group consisting of rare earth element oxide sol, anionic polymer, and cationic polymer is applied. The coating agent may further contain phosphoric acid or a phosphate, and a crosslinking agent for crosslinking the polymer. The rare earth element oxide sol has rare earth element oxide fine particles (for example, particles with an average particle size of 100 nm or less) dispersed in a liquid dispersion medium. Examples of rare earth element oxides include cerium oxide, yttrium oxide, neodymium oxide, and lanthanum oxide, and cerium oxide is preferred from the viewpoint of further improving adhesion. The rare earth element oxide contained in the corrosion-resistant film can be used alone or in combination of two or more. Examples of the liquid dispersion medium for the rare earth element oxide sol include various solvents such as water, alcohol-based solvents, hydrocarbon-based solvents, ketone-based solvents, ester-based solvents, and ether-based solvents, and water is preferred. As the cationic polymer, for example, polyethyleneimine, an ionic polymer complex consisting of a polymer having polyethyleneimine and a carboxylic acid, a primary amine grafted acrylic resin in which a primary amine is graft-polymerized to an acrylic main skeleton, polyallylamine or its derivative, aminated phenol, etc. are preferable. In addition, as the anionic polymer, poly(meth)acrylic acid or its salt, or a copolymer mainly composed of (meth)acrylic acid or its salt, is preferable. In addition, it is preferable that the crosslinking agent is at least one selected from the group consisting of a compound having any one of a functional group of an isocyanate group, a glycidyl group, a carboxyl group, and an oxazoline group, and a silane coupling agent. In addition, it is preferable that the phosphoric acid or the phosphoric acid salt is a condensed phosphoric acid or a condensed phosphate salt.
[0063] One example of a corrosion-resistant coating is one formed by applying a solution of fine particles of metal oxides such as aluminum oxide, titanium oxide, cerium oxide, and tin oxide, or barium sulfate dispersed in phosphoric acid to the surface of a barrier layer and baking the coating at 150°C or higher.
[0064] If necessary, the corrosion-resistant coating may have a laminated structure in which at least one of a cationic polymer and an anionic polymer is further laminated. Examples of the cationic polymer and anionic polymer include those mentioned above.
[0065] The composition of the corrosion-resistant film can be analyzed by, for example, time-of-flight secondary ion mass spectrometry.
[0066] The amount of the corrosion-resistant film formed on the surface of the barrier layer 3 in the chemical conversion treatment is not particularly limited. For example, in the case of coating-type chromate treatment, the amount of the corrosion-resistant film formed on the surface of the barrier layer 3 is preferably 1 mm. 2 It is desirable that the chromate compound is contained in an amount, calculated as chromium, of about 0.5 to 50 mg, preferably about 1.0 to 40 mg, the phosphorus compound is contained in an amount, calculated as phosphorus, of about 0.5 to 50 mg, preferably about 1.0 to 40 mg, and the aminated phenol polymer is contained in an amount, calculated as phosphorus, of about 1.0 to 200 mg, preferably about 5.0 to 150 mg, per unit weight of the ink.
[0067] The thickness of the corrosion-resistant film is not particularly limited, but is preferably about 1 nm to 20 μm, more preferably about 1 nm to 100 nm, and even more preferably about 1 nm to 50 nm, from the viewpoint of the cohesive strength of the film and the adhesive strength with the barrier layer and the heat-sealable resin layer. The thickness of the corrosion-resistant film can be measured by observation with a transmission electron microscope, or a combination of observation with a transmission electron microscope and energy dispersive X-ray spectroscopy or electron energy loss spectroscopy. Analysis of the composition of the corrosion-resistant film using time-of-flight secondary ion mass spectrometry can reveal that, for example, secondary ions consisting of Ce, P, and O (e.g., Ce 2 PO 4 + , CePO 4 - At least one of the above) and secondary ions consisting of, for example, Cr, P and O (e.g., CrPO 2 + , CrPO 4 - Peaks derived from at least one of the above are detected.
[0068] The chemical conversion treatment is carried out by applying a solution containing a compound used for forming a corrosion-resistant film to the surface of the barrier layer by a bar coating method, a roll coating method, a gravure coating method, a dipping method, or the like, and then heating the barrier layer so that the temperature of the barrier layer becomes about 70 to 200°C. In addition, before applying the chemical conversion treatment to the barrier layer, the barrier layer may be subjected to a degreasing treatment by an alkali dipping method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or the like. By carrying out the degreasing treatment in this manner, it becomes possible to carry out the chemical conversion treatment of the surface of the barrier layer more efficiently. In addition, by using an acid degreasing agent in which a fluorine-containing compound is dissolved in an inorganic acid for the degreasing treatment, it is possible to not only degrease the metal foil but also form a fluoride of the metal that is in a passive state, and in such a case, only the degreasing treatment may be carried out.
[0069] [Thermal adhesive resin layer 4] In the exterior packaging material for an electricity storage device of the present disclosure, the heat-sealable resin layer 4 is located on the inner layer side, and is a layer (sealant layer) that exhibits the function of sealing the electricity storage device element by heat fusion of the heat-sealable resin layer when assembling the electricity storage device. In the exterior packaging material for an electricity storage device 10 of the present disclosure, the heat-sealable resin layer 4 is composed of a single layer or multiple layers, and among the heat-sealable resin layers 4, the first heat-sealable resin layer 41 constitutes the surface of the laminate. Therefore, when assembling the electricity storage device, the first heat-sealable resin layer 41 is heat-sealed to seal the electricity storage device element.
[0070] When the thermally adhesive resin layer 4 is configured as a single layer, the thermally adhesive resin layer 4 constitutes a first thermally adhesive resin layer 41. Fig. 1 and Fig. 2 show a laminated structure in which the thermally adhesive resin layer 4 is configured as a single layer of the first thermally adhesive resin layer 41, and the first thermally adhesive resin layer 41 constitutes the surface of the laminate.
[0071] Furthermore, when the heat-sealable resin layer 4 is configured as a multilayer structure, it includes, in order from the surface side of the laminate constituting the exterior material 10 for an electricity storage device, at least a first heat-sealable resin layer 41 and a second heat-sealable resin layer 42. Fig. 3 to Fig. 5 show a laminate structure in which the heat-sealable resin layer 4 is configured as a multilayer structure (two layers) of the first heat-sealable resin layer 41 and the second heat-sealable resin layer 42, and the first heat-sealable resin layer 41 forms the surface of the laminate.
[0072] When the heat-fusible resin layer 4 is configured with multiple layers, the heat-fusible resin layer 4 may further include a third heat-fusible resin layer, a fourth heat-fusible resin layer, etc. on the barrier layer 3 side of the second heat-fusible resin layer 42 in addition to the first heat-fusible resin layer 41 and the second heat-fusible resin layer 42. When the heat-fusible resin layer 4 is configured with multiple layers, the heat-fusible resin layer 4 is preferably configured with two layers, the first heat-fusible resin layer 41 and the second heat-fusible resin layer 42.
[0073] The exterior packaging material for an electricity storage device according to the present disclosure is characterized in that the logarithmic decrement ΔE of the first thermally adhesive resin layer 41 at 140° C. in a rigid pendulum measurement is 0.20 or less. In the present disclosure, the logarithmic decrement ΔE at 140° C. is 0.20 or less, so that crushing during thermal fusion of the first thermally adhesive resin layer 41 is effectively suppressed.
[0074] The logarithmic attenuation at 140°C in the rigid pendulum measurement is an index of the hardness of the resin in a high-temperature environment of 140°C, and the smaller the logarithmic attenuation, the higher the hardness of the resin. The temperature when the heat-sealing resin layer is heat-sealed is high, and in the heat-sealed portion formed by heat-sealing the heat-sealing resin layer, the heat-sealing resin layer may protrude significantly toward the inside of the heat-sealed portion (the space side where the energy storage device element is accommodated). If the heat-sealing resin layer 4 protrudes significantly toward the inside of the heat-sealed portion, cracks will occur in the heat-sealed resin layer 4 starting from this protrusion (so-called poly pool), and the insulation will tend to deteriorate. FIG. 11 shows a schematic cross-sectional view in which a protrusion A is formed inside the heat-sealed portion of the heat-sealing resin layer 4. As shown in this cross-sectional view, the protrusion A has end points A1 and A2, and these end points A1 and A2 are structurally likely to be the starting points of cracks. Therefore, when the heat-sealable resin layer 4 protrudes largely inside the heat-sealed portion to form a protruding portion, the insulation is likely to be deteriorated due to cracks. For this reason, it is important to control the shape of the heat-sealed portion, and for this purpose, the hardness of the heat-sealable resin layer at high temperatures is important. For this reason, in the present invention, the logarithmic attenuation rate at a high temperature of 140°C is adopted. In the rigid pendulum measurement, the attenuation rate of the pendulum is measured when the temperature of the resin is increased from a low temperature to a high temperature. In the rigid pendulum measurement, generally, the edge portion is brought into contact with the surface of the object to be measured, and the object to be measured is caused to swing in the left-right direction to impart vibration to the object to be measured. In the exterior material for an electric storage device of the present invention, the first heat-sealable resin layer 41, which is hard and has a logarithmic attenuation rate of 0.20 or less in a high-temperature environment of 140°C, is disposed on the surface of the exterior material for an electric storage device, thereby suppressing the crushing (thinning) of the first heat-sealable resin layer 41 during the heat fusion of the exterior material for an electric storage device. By suppressing the crushing of the first heat-sealable resin layer 41, the heat-sealed portion formed by heat-sealing the heat-sealable resin layer is prevented from protruding significantly toward the inside of the heat-sealed portion, and the deterioration of the insulating properties of the exterior material for an electricity storage device due to heat fusion is effectively suppressed.
[0075] The logarithmic decrement ΔE is calculated by the following formula. ΔE=[ln(A1 / A2)+ln(A2 / A3)+...ln(An / An+1)] / n A: Amplitude n: wave number
[0076] In the exterior packaging material for an electricity storage device of the present invention, from the viewpoint of effectively suppressing crushing of the first heat-sealable resin layer 41 when the first heat-sealable resin layer 41 is heat-sealed, the logarithmic decrement ΔE at 140° C. is preferably about 0.10 or more, more preferably about 0.11 or more, and even more preferably about 0.12 or more, and is preferably about 0.18 or less, more preferably about 0.15 or less, and even more preferably about 0.16 or less. The range is preferably about 0.10 to 0.20, about 0.10 to 0.18, about 0.10 to 0.15, about 0.10 to 0.13, about 0.11 to 0.20, about 0.11 to 0.18, about 0.11 to 0.15, about 0.11 to 0.13, about 0.12 to 0.20, about 0.12 to 0.18, about 0.12 to 0.15, and about 0.12 to 0.13.
[0077] In addition, in the exterior material for an electric storage device of the present disclosure, from the viewpoint of effectively suppressing the crushing of the first heat-sealable resin layer 41 when the first heat-sealable resin layer 41 is heat-sealed, the logarithmic attenuation factor ΔE at 80° C. in rigid pendulum measurement of the first heat-sealable resin layer 41 is preferably more than 0.08, more preferably about 0.09 or more, and even more preferably about 0.10 or more. In addition, in the exterior material for an electric storage device of the present disclosure, the logarithmic attenuation factor ΔE at 80° C. in rigid pendulum measurement of the first heat-sealable resin layer 41 is preferably about 0.20 or less, more preferably about 0.18 or less, and even more preferably about 0.15 or less. Preferred ranges of the logarithmic decrement ΔE are more than 0.08 and not more than 0.20, more than 0.08 and not more than 0.18, more than 0.08 and not more than 0.15, about 0.09 to 0.20, about 0.09 to 0.18 degrees, about 0.09 to 0.15, about 0.10 to 0.20, about 0.10 to 0.18 degrees, and about 0.10 to 0.15.
[0078] The logarithmic attenuation rate ΔE at 80°C in the rigid pendulum measurement of the first thermally adhesive resin layer 41 is measured in the same manner as in the method for measuring the logarithmic attenuation rate ΔE at 140°C described above, except that the logarithmic attenuation rate ΔE when the surface temperature of the first thermally adhesive resin layer 41 is 80°C is used.
[0079] The logarithmic decrement ΔE of the first thermally adhesive resin layer 41 can be adjusted by, for example, the melt mass flow rate (MFR), molecular weight, melting point, softening point, molecular weight distribution, degree of crystallinity, etc. of the resin constituting the first thermally adhesive resin layer 41.
[0080] In measuring the logarithmic attenuation rate ΔE, a rigid pendulum physical test is performed on the first heat-sealable resin layer 41 using a commercially available rigid pendulum physical tester under the conditions of a cylindrical cylinder edge as the edge portion pressed against the first heat-sealable resin layer 41, an initial amplitude of 0.3 degrees, and a temperature rise rate of 3°C / min in the temperature range of 30°C to 200°C. Based on the logarithmic attenuation rate at 140°C, a standard for suppressing the collapse exhibited by the first heat-sealable resin layer 41 described later is determined. For the first heat-sealable resin layer 41 for measuring the logarithmic attenuation rate ΔE, the exterior material for an electric storage device is immersed in 15% hydrochloric acid, the base layer and the barrier layer are dissolved, and the resulting sample is thoroughly dried and used as the measurement target. When the exterior material for an electric storage device has an adhesive layer 5 described later, a laminate of the adhesive layer 5 and the heat-sealable resin layer 4 is used as the sample.
[0081] It is also possible to obtain the exterior material for an electricity storage device from the electricity storage device and measure the logarithmic decrement ΔE of the first thermally adhesive resin layer 41. When obtaining the exterior material for an electricity storage device from the electricity storage device and measuring the logarithmic decrement ΔE of the first thermally adhesive resin layer 41, a sample is cut out from the top surface portion where the exterior material for an electricity storage device is not stretched by molding and used as the measurement subject.
[0082] In addition, in the exterior material for a power storage device of the present invention, after the heat-sealing resin layers of the laminate constituting the exterior material for a power storage device are placed opposite each other and heated and pressed in the lamination direction under conditions of a temperature of 190°C, a surface pressure of 2.0 MPa, and a time of 3 seconds, the remaining ratio of the total thickness of the two first heat-sealing resin layers 41 is preferably about 30% or more, more preferably about 32% or more, and more preferably about 34% or more, and preferred ranges include 30 to 60%, 32 to 60%, 34 to 60%, 30 to 50%, 32 to 50%, and 34 to 50%. The upper limit of the remaining ratio of the thickness is, for example, about 60% or about 50%. The remaining ratio of the thickness is a value measured by the following method. In order to set the remaining ratio of the thickness, for example, the type, composition, molecular weight, etc. of the resin constituting the first heat-sealing resin layer 41 are adjusted.
[0083] <Measurement of remaining ratio of thickness of first heat-sealable resin layer> The exterior material for a power storage device is cut to a length of 150 mm and a width of 60 mm to prepare a test sample. Next, the first heat-sealable resin layers 41 of the test samples are placed opposite each other. Next, in this state, a metal plate with a width of 7 mm is used to heat and pressurize both sides of the test sample in the stacking direction under conditions of a temperature of 190° C., a surface pressure of 0.5 MPa, and a time of 3 seconds to heat-seal the first heat-sealable resin layer 41. Next, the heat-sealed portion of the test sample is cut in the stacking direction using a microtome, and the total thickness of the two first heat-sealable resin layers 41 that are heat-sealed to each other is measured for the exposed cross section. The test sample before heat-sealing is also cut in the stacking direction using a microtome in the same manner, and the thickness of the two first heat-sealable resin layers 41 is measured for the exposed cross section. The ratio of the total thickness of the two first heat-sealable resin layers 41 after heat fusion to the total thickness of the two first heat-sealable resin layers 41 before heat fusion is calculated to measure the remaining ratio (%) of the total thickness of the two first heat-sealable resin layers 41. The thicknesses of the two first heat-sealable resin layers 41 in the heat-sealed portion are measured at a location where the thickness of the exterior material for an electricity storage device is constant.
[0084] It is also possible to obtain the exterior material for an electricity storage device from the electricity storage device and measure the remaining percentage of the total thickness of the two first thermally adhesive resin layers 41. When obtaining the exterior material for an electricity storage device from the electricity storage device and measuring the remaining percentage of the total thickness of the two first thermally adhesive resin layers 41, a sample is cut out from the top surface portion where the exterior material for an electricity storage device has not been stretched by molding and used as the measurement subject.
[0085] The resin constituting the first thermally adhesive resin layer 41 is not particularly limited as long as it is thermally adhesive and the logarithmic decrement ΔE of the first thermally adhesive resin layer 41 is 0.20 or less.
[0086] The resin constituting the first thermally adhesive resin layer 41 is preferably a resin containing a polyolefin skeleton, such as polyolefin or acid-modified polyolefin. The inclusion of a polyolefin skeleton in the resin constituting the first thermally adhesive resin layer 41 can be determined by, for example, infrared spectroscopy, gas chromatography mass spectrometry, or the like. When the resin constituting the first thermally adhesive resin layer 41 is analyzed by infrared spectroscopy, it is preferable that a peak derived from maleic anhydride is detected. For example, when maleic anhydride-modified polyolefin is measured by infrared spectroscopy, a peak derived from maleic anhydride is detected at a wave number of 1760 cm. -1 Nearby and wave number 1780cm -1 A peak derived from maleic anhydride is detected near the peak. When the first thermally adhesive resin layer 41 is a layer made of maleic anhydride-modified polyolefin, a peak derived from maleic anhydride is detected by infrared spectroscopy. However, if the degree of acid modification is low, the peak becomes small and may not be detected. In that case, analysis can be performed by nuclear magnetic resonance spectroscopy.
[0087] Specific examples of polyolefins include polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene; ethylene-α-olefin copolymers; polypropylenes such as homopolypropylene, block copolymers of polypropylene (e.g., block copolymers of propylene and ethylene), and random copolymers of polypropylene (e.g., random copolymers of propylene and ethylene); propylene-α-olefin copolymers; and ethylene-butene-propylene terpolymers. Among these, polypropylene is preferred. When the polyolefin resin is a copolymer, it may be a block copolymer or a random copolymer. These polyolefin resins may be used alone or in combination of two or more.
[0088] The polyolefin may be a cyclic polyolefin. The cyclic polyolefin is a copolymer of an olefin and a cyclic monomer, and examples of the olefins constituting the cyclic polyolefin include ethylene, propylene, 4-methyl-1-pentene, styrene, butadiene, and isoprene. Examples of the cyclic monomers constituting the cyclic polyolefin include cyclic alkenes such as norbornene; and cyclic dienes such as cyclopentadiene, dicyclopentadiene, cyclohexadiene, and norbornadiene. Among these, cyclic alkenes are preferred, and norbornene is more preferred.
[0089] The acid-modified polyolefin is a polymer modified by block polymerization or graft polymerization of a polyolefin with an acid component. The polyolefin to be modified with an acid may be the above-mentioned polyolefin, a copolymer obtained by copolymerizing the above-mentioned polyolefin with a polar molecule such as acrylic acid or methacrylic acid, or a polymer such as a crosslinked polyolefin. The acid component used for the acid modification may be, for example, a carboxylic acid or an anhydride such as maleic acid, acrylic acid, itaconic acid, crotonic acid, maleic anhydride, or itaconic anhydride.
[0090] The acid-modified polyolefin may be an acid-modified cyclic polyolefin. The acid-modified cyclic polyolefin is a polymer obtained by copolymerizing a part of the monomers constituting the cyclic polyolefin by replacing it with an acid component, or by block-polymerizing or graft-polymerizing an acid component to the cyclic polyolefin. The cyclic polyolefin to be acid-modified is the same as described above. The acid component used for the acid modification is the same as the acid component used for the modification of the polyolefin.
[0091] Preferred acid-modified polyolefins include polyolefins modified with a carboxylic acid or anhydride thereof, polypropylenes modified with a carboxylic acid or anhydride thereof, maleic anhydride-modified polyolefins, and maleic anhydride-modified polypropylenes.
[0092] The first thermally adhesive resin layer 41 may be formed of one type of resin alone, or may be formed of a blend polymer of two or more types of resins.
[0093] The first heat-sealable resin layer 41 constituting the surface preferably contains polyolefin. For example, in the exterior material 10 for an electric storage device of the present disclosure, when the heat-sealable resin layer 4 includes the first heat-sealable resin layer 41 and the second heat-sealable resin layer 42, it is preferable that the first heat-sealable resin layer 41 constituting the surface contains polyolefin, and the second heat-sealable resin layer 42 contains acid-modified polyolefin. In addition, in the exterior material 10 for an electric storage device of the present disclosure, when the adhesive layer 5 is included, it is preferable that the first heat-sealable resin layer 41 constituting the surface contains polyolefin, and the adhesive layer 5 contains acid-modified polyolefin. In addition, it is preferable that the adhesive layer 5 contains acid-modified polyolefin, the first heat-sealable resin layer contains polyolefin, and the second heat-sealable resin layer contains polyolefin, and it is more preferable that the adhesive layer 5 contains acid-modified polypropylene, the first heat-sealable resin layer contains polypropylene, and the second heat-sealable resin layer contains polypropylene.
[0094] The first thermally adhesive resin layer 41 may contain a lubricant, etc., if necessary. When the first thermally adhesive resin layer 41 contains a lubricant, the moldability of the exterior material for an electrical storage device can be improved. The lubricant is not particularly limited, and a known lubricant can be used. The lubricant may be used alone or in combination of two or more kinds.
[0095] The lubricant is not particularly limited, but preferably includes an amide-based lubricant. Specific examples of the lubricant include those exemplified for the base layer 1. The lubricant may be used alone or in combination of two or more kinds.
[0096] When a lubricant is present on the surface of the first thermally adhesive resin layer 41, the amount of the lubricant is not particularly limited. From the viewpoint of improving the formability of the exterior material for an electrical storage device, the amount of the lubricant is preferably 10 to 50 mg / m 2 about 15 to 40 mg / m 2 In addition, even when a lubricant is present on the surface of the first thermally adhesive resin layer 41, the first thermally adhesive resin layer 41, including the lubricant, constitutes the surface of the exterior packaging material 10 for an electricity storage device.
[0097] The lubricant present on the surface of the first heat-sealable resin layer 41 may be a lubricant exuded from the resin constituting the first heat-sealable resin layer 41, or a lubricant applied to the surface of the first heat-sealable resin layer 41.
[0098] Furthermore, the thickness of the first thermally adhesive resin layer 41 is not particularly limited as long as the thermally adhesive resin layer exhibits the function of thermally sealing the electricity storage device element.
[0099] From the viewpoint of effectively suppressing crushing when the first heat-sealable resin layer 41 is heat-sealed, the thickness of the first heat-sealable resin layer 41 is preferably about 100 μm or less, about 85 μm or less, or about 60 μm or less, and also 5 μm or more, 10 μm or more, 20 μm or more, 30 μm or more, or 40 μm or more. Preferred ranges include about 5 to 100 μm, about 5 to 85 μm, about 5 to 60 μm, about 10 to 100 μm, about 10 to 85 μm, about 10 to 60 μm, about 20 to 100 μm, about 20 to 85 μm, about 20 to 60 μm, about 30 to 100 μm, about 30 to 85 μm, about 30 to 60 μm, about 40 to 100 μm, about 40 to 85 μm, and about 40 to 60 μm.
[0100] Specifically, from the viewpoint of effectively suppressing crushing when the first heat-sealable resin layer 41 is heat-sealed, when the heat-sealable resin layer 4 is composed of a single layer of the first heat-sealable resin layer 41, the thickness of the first heat-sealable resin layer 41 is preferably about 100 μm or less, about 85 μm or less, about 60 μm or less, or about 25 μm or less, and further preferably 5 μm or more, 10 μm or more, 20 μm or more, 30 μm or more, or 40 μm or more. Examples of the thickness include about 5 to 100 μm, about 5 to 85 μm, about 5 to 60 μm, about 5 to 25 μm, about 10 to 100 μm, about 10 to 85 μm, about 10 to 60 μm, about 10 to 25 μm, about 20 to 100 μm, about 20 to 85 μm, about 20 to 60 μm, about 20 to 25 μm, about 30 to 100 μm, about 30 to 85 μm, about 30 to 60 μm, about 40 to 100 μm, about 40 to 85 μm, and about 40 to 60 μm.
[0101] Furthermore, from the viewpoint of effectively suppressing crushing when the first heat-sealable resin layer 41 is heat-sealed and enhancing the sealing performance of the exterior material for an electricity storage device, when the heat-sealable resin layer 4 includes the first heat-sealable resin layer 41 and the second heat-sealable resin layer 42, the thickness of the first heat-sealable resin layer 41 is preferably about 85 μm or less, about 60 μm or less, or about 25 μm or less, and further preferably 5 μm or more, 10 μm or more. , 20 μm or more, 30 μm or more, and 40 μm or more, and preferred ranges include about 5 to 85 μm, about 5 to 60 μm, about 5 to 25 μm, about 10 to 85 μm, about 10 to 60 μm, about 10 to 25 μm, about 20 to 85 μm, about 20 to 60 μm, about 20 to 25 μm, about 30 to 85 μm, about 30 to 60 μm, about 40 to 85 μm, and about 40 to 60 μm.
[0102] When the thermally adhesive resin layer 4 includes the second thermally adhesive resin layer 42, the resin constituting the second thermally adhesive resin layer 42 is preferably a resin containing a polyolefin skeleton, such as polyolefin or acid-modified polyolefin. These resins are the same as those described for the first thermally adhesive resin layer 41. The fact that the resin constituting the second thermally adhesive resin layer 42 contains a polyolefin skeleton can be analyzed, for example, by infrared spectroscopy, gas chromatography mass spectrometry, or the like. In addition, when the resin constituting the second thermally adhesive resin layer 42 is analyzed by infrared spectroscopy, it is preferable that a peak derived from maleic anhydride is detected. For example, when maleic anhydride-modified polyolefin is measured by infrared spectroscopy, a peak derived from maleic anhydride is detected at a wave number of 1760 cm. -1 Nearby and wave number 1780cm -1 A peak derived from maleic anhydride is detected near the peak. When the second heat-sealable resin layer 42 is a layer made of maleic anhydride-modified polyolefin, a peak derived from maleic anhydride is detected by infrared spectroscopy. However, if the degree of acid modification is low, the peak becomes small and may not be detected. In that case, analysis can be performed by nuclear magnetic resonance spectroscopy.
[0103] The second heat-sealable resin layer 42 preferably contains polyolefin. In particular, when the heat-sealable resin layer 4 includes the first heat-sealable resin layer 41 and the second heat-sealable resin layer 42, and includes the adhesive layer 5 described below, the second heat-sealable resin layer 42 preferably contains polyolefin. As described above, in the exterior packaging material 10 for an electric storage device of the present disclosure, when the heat-sealable resin layer 4 includes the first heat-sealable resin layer 41 and the second heat-sealable resin layer 42, and does not include the adhesive layer 5 described below, it is preferable that the first heat-sealable resin layer 41 constituting the surface contains polyolefin, and the second heat-sealable resin layer 42 contains acid-modified polyolefin.
[0104] The thickness of the second heat-sealable resin layer 42 is not particularly limited as long as the heat-sealable resin layer 42 exhibits the function of heat-sealing the electricity storage device element by heat fusion.
[0105] From the viewpoint of effectively suppressing the collapse when the first heat-sealable resin layer 41 is heat-sealed and enhancing the sealing performance of the electrical storage device exterior material, the thickness of the second heat-sealable resin layer 42 is preferably larger than the thickness of the first heat-sealable resin layer 41. The first heat-sealable resin layer 41 is preferably made of a resin that flows easily at high temperatures so as to have excellent thermal adhesion. By providing such a thickness relationship, the first heat-sealable resin layer 41, which is a part of the thermal fusion resin layer 4 and is made of a resin that flows easily, can be made thin, thereby improving the insulation of the electrical storage device exterior material. By appropriately adjusting the MFR, melting point, molecular weight, etc. of the resin that constitutes the first heat-sealable resin layer 41, it is possible to make the first heat-sealable resin layer 41 a resin layer that flows easily at high temperatures.
[0106] From the viewpoint of effectively suppressing crushing when the first heat-sealable resin layer 41 is heat-sealed and improving the sealing performance of the exterior material for an electricity storage device, the thickness of the second heat-sealable resin layer 42 is preferably about 100 μm or less, about 85 μm or less, or about 60 μm or less, and also preferably 5 μm or more, 10 μm or more, 20 μm or more, 30 μm or more, or 40 μm or more. Examples of the thickness include about 5 to 100 μm, about 5 to 85 μm, about 5 to 60 μm, about 10 to 100 μm, about 10 to 85 μm, about 10 to 60 μm, about 20 to 100 μm, about 20 to 85 μm, about 20 to 60 μm, about 30 to 100 μm, about 30 to 85 μm, about 30 to 60 μm, about 40 to 100 μm, about 40 to 85 μm, and about 40 to 60 μm.
[0107] The heat-sealable resin layer 4 may further include other heat-sealable resin layers, such as a third heat-sealable resin layer and a fourth heat-sealable resin layer, on the barrier layer 3 side of the second heat-sealable resin layer 42 in addition to the first heat-sealable resin layer 41 and the second heat-sealable resin layer 42. Examples of resins constituting the other heat-sealable resin layers include those described for the first heat-sealable resin layer 41. Examples of thicknesses of the other heat-sealable resin layers include those described for the second heat-sealable resin layer 42.
[0108] The total thickness of the heat-fusible resin layer 4 is preferably about 100 μm or less, about 85 μm or less, or about 60 μm or less, and also 5 μm or more, 10 μm or more, 20 μm or more, 30 μm or more, or 40 μm or more. Preferred ranges include about 5 to 100 μm, about 5 to 85 μm, about 5 to 60 μm, about 10 to 100 μm, about 10 to 85 μm, about 10 to 60 μm, about 20 to 100 μm, about 20 to 85 μm, about 20 to 60 μm, about 30 to 100 μm, about 30 to 85 μm, about 30 to 60 μm, about 40 to 100 μm, about 40 to 85 μm, and about 40 to 60 μm.
[0109] [Adhesive layer 5] In the packaging material for an electricity storage device of the present disclosure, the adhesive layer 5 is a layer that is provided, if necessary, between the barrier layer 3 (or the corrosion-resistant film) and the heat-sealable resin layer 4 in order to firmly bond them together.
[0110] The adhesive layer 5 is formed of a resin capable of bonding the barrier layer 3 and the heat-sealable resin layer 4. The resin used to form the adhesive layer 5 may be, for example, the same adhesive as exemplified for the adhesive layer 2. The resin used to form the adhesive layer 5 preferably contains a polyolefin skeleton, and examples thereof include the polyolefin and acid-modified polyolefin exemplified for the first heat-sealable resin layer 41. The resin constituting the adhesive layer 5 can be analyzed to determine whether it contains a polyolefin skeleton, for example, by infrared spectroscopy, gas chromatography mass spectrometry, or the like, and the analysis method is not particularly limited. In addition, when the resin constituting the adhesive layer 5 is analyzed by infrared spectroscopy, it is preferable that a peak derived from maleic anhydride is detected. For example, when maleic anhydride-modified polyolefin is measured by infrared spectroscopy, a peak derived from maleic anhydride is detected at a wave number of 1760 cm. -1 Nearby and wave number 1780cm -1 A peak derived from maleic anhydride is detected around this peak. However, if the degree of acid modification is low, the peak may be small and not detectable. In that case, analysis can be performed using nuclear magnetic resonance spectroscopy.
[0111] The adhesive layer 5 can be formed from a thermoplastic resin or a cured product of a thermosetting resin, and is preferably formed from a thermoplastic resin.
[0112] From the viewpoint of firmly adhering the barrier layer 3 and the heat-fusible resin layer 4, the adhesive layer 5 preferably contains an acid-modified polyolefin. Particularly preferred examples of the acid-modified polyolefin include polyolefins modified with carboxylic acid or its anhydride, polypropylenes modified with carboxylic acid or its anhydride, maleic anhydride-modified polyolefins, and maleic anhydride-modified polypropylenes.
[0113] Furthermore, from the viewpoint of reducing the thickness of the electrical storage device exterior material while providing an electrical storage device exterior material with excellent shape stability after molding, the adhesive layer 5 is more preferably a cured product of a resin composition containing an acid-modified polyolefin and a curing agent. Preferred examples of the acid-modified polyolefin include those mentioned above.
[0114] As described above, in the exterior packaging material 10 for an electricity storage device according to the present disclosure, when the adhesive layer 5 is provided, it is preferable that the first heat-sealable resin layer 41 constituting the surface contains a polyolefin, and the adhesive layer 5 contains an acid-modified polyolefin.
[0115] The adhesive layer 5 is preferably a cured product of a resin composition containing an acid-modified polyolefin and at least one selected from the group consisting of a compound having an isocyanate group, a compound having an oxazoline group, and a compound having an epoxy group, and is particularly preferably a cured product of a resin composition containing an acid-modified polyolefin and at least one selected from the group consisting of a compound having an isocyanate group and a compound having an epoxy group. The adhesive layer 5 is preferably at least one selected from the group consisting of polyurethane, polyester, and epoxy resin, and more preferably contains polyurethane and epoxy resin. As the polyester, for example, an amide ester resin is preferable. Amide ester resins are generally produced by the reaction of a carboxyl group and an oxazoline group. The adhesive layer 5 is more preferably a cured product of a resin composition containing at least one of these resins and the acid-modified polyolefin. In addition, if unreacted compounds such as a compound having an isocyanate group, a compound having an oxazoline group, or a curing agent such as an epoxy resin remain in the adhesive layer 5, the presence of the unreacted compounds can be confirmed by a method selected from, for example, infrared spectroscopy, Raman spectroscopy, time-of-flight secondary ion mass spectrometry (TOF-SIMS), etc.
[0116] In addition, from the viewpoint of further increasing the adhesion between the barrier layer 3 and the adhesive layer 5, the adhesive layer 5 is preferably a cured product of a resin composition containing a curing agent having at least one selected from the group consisting of an oxygen atom, a heterocycle, a C=N bond, and a COC bond. Examples of the curing agent having a heterocycle include a curing agent having an oxazoline group and a curing agent having an epoxy group. Examples of the curing agent having a C=N bond include a curing agent having an oxazoline group and a curing agent having an isocyanate group. Examples of the curing agent having a COC bond include a curing agent having an oxazoline group, a curing agent having an epoxy group, and polyurethane. It can be confirmed that the adhesive layer 5 is a cured product of a resin composition containing these curing agents by, for example, gas chromatography mass spectrometry (GCMS), infrared spectroscopy (IR), time-of-flight secondary ion mass spectrometry (TOF-SIMS), X-ray photoelectron spectroscopy (XPS), or other methods.
[0117] The compound having an isocyanate group is not particularly limited, but from the viewpoint of effectively increasing the adhesion between the barrier layer 3 and the adhesive layer 5, a polyfunctional isocyanate compound is preferably used. The polyfunctional isocyanate compound is not particularly limited as long as it is a compound having two or more isocyanate groups. Specific examples of polyfunctional isocyanate-based curing agents include pentane diisocyanate (PDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), polymerized or nurated products thereof, mixtures thereof, and copolymers with other polymers. In addition, adducts, biuret products, isocyanurates, etc. are also included.
[0118] The content of the compound having an isocyanate group in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, and more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This makes it possible to effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5.
[0119] The compound having an oxazoline group is not particularly limited as long as it is a compound having an oxazoline skeleton. Specific examples of the compound having an oxazoline group include those having a polystyrene main chain and those having an acrylic main chain. In addition, examples of commercially available products include the Epocross series manufactured by Nippon Shokubai Co., Ltd.
[0120] The proportion of the compound having an oxazoline group in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, and more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This can effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5.
[0121] An example of a compound having an epoxy group is an epoxy resin. The epoxy resin is not particularly limited as long as it is a resin capable of forming a crosslinked structure by the epoxy group present in the molecule, and a known epoxy resin can be used. The weight average molecular weight of the epoxy resin is preferably about 50 to 2000, more preferably about 100 to 1000, and even more preferably about 200 to 800. In the present disclosure, the weight average molecular weight of the epoxy resin is a value measured by gel permeation chromatography (GPC) under conditions using polystyrene as a standard sample.
[0122] Specific examples of epoxy resins include glycidyl ether derivatives of trimethylolpropane, bisphenol A diglycidyl ether, modified bisphenol A diglycidyl ether, novolac glycidyl ether, glycerin polyglycidyl ether, polyglycerin polyglycidyl ether, etc. The epoxy resins may be used alone or in combination of two or more.
[0123] The ratio of the epoxy resin in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, and more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This can effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5.
[0124] The polyurethane is not particularly limited, and any known polyurethane can be used. The adhesive layer 5 may be, for example, a cured product of a two-component curing polyurethane.
[0125] The proportion of polyurethane in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, and more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This makes it possible to effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5 in an atmosphere containing a component that induces corrosion of the barrier layer, such as an electrolyte solution.
[0126] In addition, when the adhesive layer 5 is a cured product of a resin composition containing at least one selected from the group consisting of a compound having an isocyanate group, a compound having an oxazoline group, and an epoxy resin, and the acid-modified polyolefin, the acid-modified polyolefin functions as a main agent, and the compound having an isocyanate group, the compound having an oxazoline group, and the compound having an epoxy group each function as a curing agent.
[0127] From the viewpoint of effectively suppressing crushing when the first heat-sealable resin layer 41 is heat-sealed and improving the sealing performance of the exterior material for an electricity storage device, the total thickness of the adhesive layer 5 and the heat-sealable resin layer 4 is preferably about 50 μm or more, more preferably about 60 μm or more, and even more preferably about 70 μm or more, and is preferably about 120 μm or less, more preferably about 100 μm or less, and preferred ranges include about 50 to 120 μm, about 50 to 100 μm, about 60 to 120 μm, about 60 to 100 μm, about 70 to 120 μm, and about 70 to 100 μm.
[0128] Furthermore, a preferred ratio between the thickness of the first heat-sealable resin layer 41 and the thickness of the second heat-sealable resin layer 42 is such that, when the thickness of the first heat-sealable resin layer 41 is 1.0, the thickness of the second heat-sealable resin layer 42 is preferably about 1.5 to 6.0, more preferably about 1.7 to 5.5, and even more preferably about 2.0 to 5.0. Furthermore, a preferred ratio of the thickness of the adhesive layer 5 to the thickness of the first heat-sealable resin layer 41 to the thickness of the second heat-sealable resin layer 42 is such that, with the thickness of the first heat-sealable resin layer 41 being 1.0, it is preferable that the thickness of the adhesive layer 5 is approximately 0.5 to 3.0 and the thickness of the second heat-sealable resin layer 42 is approximately 1.5 to 6.0, it is more preferable that the thickness of the adhesive layer 5 is approximately 0.7 to 2.3 and the thickness of the second heat-sealable resin layer 42 is approximately 1.7 to 5.5, and it is even more preferable that the thickness of the adhesive layer 5 is approximately 1.0 to 2.0 and the thickness of the second heat-sealable resin layer 42 is approximately 2.0 to 5.0.
[0129] In addition, specific examples of preferred ratios between the thickness of the first heat-sealable resin layer 41 and the thickness of the second heat-sealable resin layer 42 include, for example, when the thickness of the first heat-sealable resin layer 41 is 1.0, the thickness of the second heat-sealable resin layer 42 is 2.0, 2.7, 3.0, 4.0, 5.0, 6.0, etc. In addition, preferred specific examples of the thickness of the adhesive layer 5, the first heat-fusible resin layer 41, and the second heat-fusible resin layer 42 include a thickness of the first heat-fusible resin layer 41 being 1.0, a thickness of the adhesive layer 5 being 1.0 and a thickness of the second heat-fusible resin layer 42 being 2.0, a thickness of the adhesive layer 5 being 1.7 and a thickness of the second heat-fusible resin layer 42 being 2.7, a thickness of the adhesive layer 5 being 1.3 and a thickness of the second heat-fusible resin layer 42 being 3.0, a thickness of the adhesive layer 5 being 2.0 and a thickness of the second heat-fusible resin layer 42 being 5.0, etc.
[0130] From the viewpoint of effectively suppressing the collapse when the first heat-sealable resin layer 41 is heat-sealed and enhancing the sealing property of the electrical storage device exterior material, the thickness of the adhesive layer 5 may be larger than the thickness of the first heat-sealable resin layer 41. For example, when the thermally adhesive resin layer 4 is composed of a single layer of the first heat-sealable resin layer 41 and has the adhesive layer 5 between the barrier layer 3 and the first heat-sealable resin layer 41, the thickness of the adhesive layer 5 is preferably equal to or larger than the thickness of the first heat-sealable resin layer 41. For the first heat-sealable resin layer 41, a resin that flows more easily at high temperatures than the adhesive layer 5 is preferably used so as to have excellent thermal fusion properties. By providing such a thickness relationship, the insulation of the electrical storage device exterior material can be improved by thinning the first heat-sealable resin layer 41, which is a part of the thermally adhesive resin layer 4 and is composed of a resin that flows easily. By appropriately adjusting the MFR, melting point, molecular weight, and the like of the resin constituting the first thermally adhesive resin layer 41, it is possible to make the first thermally adhesive resin layer 41 a resin layer that easily flows at high temperatures.
[0131] Furthermore, in the exterior packaging material for an electricity storage device 10 of the present disclosure, when the heat-sealable resin layer 4 includes a first heat-sealable resin layer 41 and a second heat-sealable resin layer 42, the thickness of the second heat-sealable resin layer 42 is preferably equal to or greater than the thickness of the adhesive layer 5. Since the second heat-sealable resin layer 42 has better moisture barrier properties than the adhesive layer 5 that contributes to adhesion, providing such a thickness relationship can improve the moisture barrier properties of the exterior packaging material for an electricity storage device.
[0132] In order to provide high insulation after heat fusion of the heat-sealable resin layer, it is preferable that the thickness of the second heat-sealable resin layer 42 is greater than the thickness of the adhesive layer 5, and that the thickness of the adhesive layer 5 is greater than the thickness of the first heat-sealable resin layer 41.
[0133] The thickness of the adhesive layer 5 is preferably about 60 μm or less, about 50 μm or less, about 40 μm or less, about 30 μm or less, about 20 μm or less, about 10 μm or less, about 8 μm or less, about 5 μm or less, or about 3 μm or less, and also preferably about 0.1 μm or more, about 0.5 μm or more, about 5 μm or more, about 10 μm or more, or about 20 μm or more, and the thickness range is preferably about 0.1 to 60 μm, about 0.1 to 50 μm, about 0.1 to 40 μm, about 0.1 to 30 μm, about 0.1 to 20 μm, about 0.1 μm to 10 μm, or about 0.1 to 8 μm. , about 0.1 to 5 μm, about 0.1 to 3 μm, about 0.5 to 60 μm, about 0.5 to 50 μm, about 0.5 to 40 μm, about 0.5 to 30 μm, about 0.5 to 20 μm, about 0.5 μm to 10 μm, about 0.5 to 8 μm, about 0.5 to 5 μm, about 0.5 to 3 μm, about 5 to 60 μm, about 5 to 50 μm, about 5 to 40 μm, about 5 to 30 μm, about 5 to 20 μm, about 5 μm to 10 μm, about 5 to 8 μm, about 10 to 60 μm, about 10 to 50 μm, about 10 to 40 μm, about 10 to 30 μm, and about 10 to 20 μm. More specifically, in the case of the adhesive layer 2 or the cured product of an acid-modified polyolefin and a curing agent, the thickness is preferably about 1 to 10 μm, more preferably 1 μm or more and less than 10 μm, even more preferably about 1 to 8 μm, even more preferably about 1 to 5 μm, and even more preferably about 1 to 3 μm. In addition, in the case of using the resin exemplified in the first heat-sealable resin layer 41, the thickness is preferably about 2 to 60 μm, about 2 to 50 μm, about 10 to 60 μm, about 10 to 50 μm, about 20 to 60 μm, and about 20 to 50 μm. In addition, in the case of the adhesive layer 5 being the adhesive layer 2 or the cured product of a resin composition containing an acid-modified polyolefin and a curing agent, for example, the adhesive layer 5 can be formed by applying the resin composition and curing it by heating or the like. In addition, in the case of using the resin exemplified in the first heat-sealable resin layer 41, the adhesive layer 5 can be formed, for example, by extrusion molding of the heat-sealable resin layer 4 and the adhesive layer 5.
[0134] In the exterior packaging material 10 for an electricity storage device of the present disclosure, specific examples of preferred laminated structures on the side opposite to the base material layer 1 side of the barrier layer 3 include, in order from the barrier layer 3 side, a laminated structure in which an adhesive layer 5 having a thickness of about 20 to 60 μm and a first heat-sealable resin layer 41 having a thickness of 20 to 50 μm are laminated; a laminated structure in which an adhesive layer 5 having a thickness of about 20 to 60 μm and a first heat-sealable resin layer 41 having a thickness of 20 to 40 μm are laminated; a laminated structure in which an adhesive layer 5 having a thickness of about 5 to 30 μm, a second heat-sealable resin layer 42 having a thickness of about 30 to 80 μm, and a first heat-sealable resin layer 41 having a thickness of about 5 to 25 μm are laminated; and a laminated structure in which an adhesive layer 5 having a thickness of about 5 to 20 μm, a second heat-sealable resin layer 42 having a thickness of about 40 to 80 μm, and a first heat-sealable resin layer 41 having a thickness of about 5 to 25 μm are laminated.
[0135] [Surface coating layer 6] The exterior material for an electricity storage device according to the present disclosure may have a surface coating layer 6 on the substrate layer 1 (the opposite side of the substrate layer 1 to the barrier layer 3) as necessary, for the purpose of improving at least one of design, electrolyte resistance, scratch resistance, formability, etc. The surface coating layer 6 is a layer located on the outermost layer side of the exterior material for an electricity storage device when an electricity storage device is assembled using the exterior material for an electricity storage device.
[0136] The surface coating layer 6 can be formed from a resin such as polyvinylidene chloride, polyester, polyurethane, acrylic resin, or epoxy resin.
[0137] When the resin forming the surface coating layer 6 is a curable resin, the resin may be either a one-component curable type or a two-component curable type, but is preferably a two-component curable type. Examples of two-component curable resins include two-component curable polyurethane, two-component curable polyester, and two-component curable epoxy resin. Among these, two-component curable polyurethane is preferred.
[0138] Examples of two-component curing polyurethane include polyurethanes containing a base material containing a polyol compound and a curing agent containing an isocyanate compound. Preferably, two-component curing polyurethanes are used in which a polyol such as polyester polyol, polyether polyol, and acrylic polyol is used as a base material, and an aromatic or aliphatic polyisocyanate is used as a curing agent. In addition, it is preferable to use a polyester polyol having a hydroxyl group on the side chain in addition to the terminal hydroxyl group of the repeating unit as the polyol compound. Since the surface coating layer 6 is formed of polyurethane, excellent electrolyte resistance is imparted to the exterior material for the electricity storage device.
[0139] The surface coating layer 6 may contain additives such as the above-mentioned lubricant, antiblocking agent, matting agent, flame retardant, antioxidant, tackifier, and antistatic agent in at least one of the surface and the inside of the surface coating layer 6, as necessary, depending on the functionality to be provided to the surface of the surface coating layer 6. Examples of the additives include fine particles having an average particle size of about 0.5 nm to 5 μm. The average particle size of the additive is the median size measured by a laser diffraction / scattering type particle size distribution measuring device.
[0140] The additive may be either inorganic or organic. The shape of the additive is not particularly limited, and examples of the shape include spherical, fibrous, plate-like, amorphous, and scaly.
[0141] Specific examples of additives include talc, silica, graphite, kaolin, montmorillonite, mica, hydrotalcite, silica gel, zeolite, aluminum hydroxide, magnesium hydroxide, zinc oxide, magnesium oxide, aluminum oxide, neodymium oxide, antimony oxide, titanium oxide, cerium oxide, calcium sulfate, barium sulfate, calcium carbonate, calcium silicate, lithium carbonate, calcium benzoate, calcium oxalate, magnesium stearate, alumina, carbon black, carbon nanotubes, high melting point nylon, acrylate resin, crosslinked acrylic, crosslinked styrene, crosslinked polyethylene, benzoguanamine, gold, aluminum, copper, nickel, etc. The additives may be used alone or in combination of two or more. Among these additives, silica, barium sulfate, and titanium oxide are preferable from the viewpoint of dispersion stability and cost. In addition, the additives may be subjected to various surface treatments such as insulation treatment and high dispersibility treatment.
[0142] The method for forming the surface coating layer 6 is not particularly limited, and examples thereof include a method for applying a resin that forms the surface coating layer 6. When an additive is blended into the surface coating layer 6, a resin mixed with the additive may be applied.
[0143] The thickness of the surface coating layer 6 is not particularly limited as long as the surface coating layer 6 exhibits the above-mentioned functions, and may be, for example, about 0.5 to 10 μm, and preferably about 1 to 5 μm.
[0144] 3. Manufacturing method for exterior material for power storage device The method for producing the exterior material for an electric storage device is not particularly limited as long as a laminate in which each layer included in the exterior material for an electric storage device of the present invention is laminated can be obtained, and examples thereof include a method including a step of laminating at least a base layer 1, a barrier layer 3, and a heat-sealable resin layer 4 in this order. In the method for producing the exterior material for an electric storage device 10 of the present disclosure, the heat-sealable resin layer 4 is composed of a single layer or multiple layers, and among the heat-sealable resin layers 4, the first heat-sealable resin layer 41 constituting the surface of the laminate has a logarithmic attenuation factor ΔE of 0.20 or less at 140° C. in a rigid pendulum measurement. The details of the exterior material for an electric storage device 10 of the present disclosure are as described above.
[0145] An example of the method for producing the exterior material for an electricity storage device of the present invention is as follows. First, a laminate (hereinafter, sometimes referred to as "laminate A") is formed in which a base layer 1, an adhesive layer 2, and a barrier layer 3 are laminated in this order. Specifically, the laminate A can be formed by a dry lamination method in which an adhesive used to form the adhesive layer 2 is applied to the base layer 1 or to the barrier layer 3, the surface of which has been chemically treated as necessary, by a coating method such as gravure coating or roll coating, and then dried, and the barrier layer 3 or base layer 1 is laminated thereon, and the adhesive layer 2 is cured.
[0146] Next, the heat-sealable resin layer 4 is laminated on the barrier layer 3 of the laminate A. When the heat-sealable resin layer 4 is directly laminated on the barrier layer 3, the heat-sealable resin layer 4 may be laminated on the barrier layer 3 of the laminate A by a method such as thermal lamination or extrusion lamination. When an adhesive layer 5 is provided between the barrier layer 3 and the heat-sealable resin layer 4, for example, (1) a method of laminating the adhesive layer 5 and the heat-sealable resin layer 4 by extruding them on the barrier layer 3 of the laminate A (co-extrusion lamination method, tandem lamination method), (2) a method of separately forming a laminate in which the adhesive layer 5 and the heat-sealable resin layer 4 are laminated, and laminating this on the barrier layer 3 of the laminate A by a thermal lamination method, or a method of forming a laminate in which the adhesive layer 5 is laminated on the barrier layer 3 of the laminate A, and laminating this on the heat-sealable resin layer 4 by a thermal lamination method. (3) a method in which a molten adhesive layer 5 is poured between the barrier layer 3 of the laminate A and a heat-sealable resin layer 4 previously formed into a sheet-like film, and the laminate A and the heat-sealable resin layer 4 are bonded together via the adhesive layer 5 (sandwich lamination method); (4) a method in which an adhesive for forming an adhesive layer 5 is solution-coated on the barrier layer 3 of the laminate A, and laminated by drying or baking, and then the heat-sealable resin layer 4 previously formed into a sheet-like film is laminated on the adhesive layer 5.
[0147] When the surface coating layer 6 is provided, the surface coating layer 6 is laminated on the surface of the base layer 1 opposite to the barrier layer 3. The surface coating layer 6 can be formed, for example, by applying the above-mentioned resin for forming the surface coating layer 6 to the surface of the base layer 1. The order of the step of laminating the barrier layer 3 on the surface of the base layer 1 and the step of laminating the surface coating layer 6 on the surface of the base layer 1 is not particularly limited. For example, after forming the surface coating layer 6 on the surface of the base layer 1, the barrier layer 3 may be formed on the surface of the base layer 1 opposite to the surface coating layer 6.
[0148] As described above, a laminate is formed which includes, in this order, the optional surface coating layer 6 / the base material layer 1 / the optional adhesive layer 2 / the barrier layer 3 / the optional adhesive layer 5 / the heat-sealable resin layer 4. In order to strengthen the adhesion of the optional adhesive layer 2 and the optional adhesive layer 5, the laminate may be subjected to a heat treatment.
[0149] In the exterior packaging material for an electricity storage device, each layer constituting the laminate may be subjected to a surface activation treatment such as corona treatment, blast treatment, oxidation treatment, ozone treatment, etc., as necessary, to improve the processability. For example, by subjecting the surface of the base layer 1 opposite to the barrier layer 3 to corona treatment, the printability of the ink on the surface of the base layer 1 can be improved.
[0150] 4. Applications of exterior materials for energy storage devices The exterior material for an electricity storage device according to the present disclosure is used in a package for hermetically housing an electricity storage device element such as a positive electrode, a negative electrode, an electrolyte, etc. That is, an electricity storage device can be formed by housing an electricity storage device element including at least a positive electrode, a negative electrode, and an electrolyte in a package formed from the exterior material for an electricity storage device according to the present disclosure.
[0151] Specifically, an electricity storage device element having at least a positive electrode, a negative electrode, and an electrolyte is covered with the exterior material for an electricity storage device of the present disclosure in such a manner that a flange portion (a region where the heat-sealable resin layers contact each other) can be formed on the periphery of the electricity storage device element with the metal terminals connected to each of the positive electrode and the negative electrode protruding outward, and the heat-sealable resin layers of the flange portion are heat-sealed to provide an electricity storage device using the exterior material for an electricity storage device. When an electricity storage device element is housed in a package formed with the exterior material for an electricity storage device of the present disclosure, the package is formed so that the heat-sealable resin portion of the exterior material for an electricity storage device of the present disclosure faces inside (the surface in contact with the electricity storage device element).
[0152] The exterior material for an electric storage device of the present disclosure can be suitably used for an electric storage device such as a battery (including a condenser, a capacitor, etc.). The exterior material for an electric storage device of the present disclosure may be used for either a primary battery or a secondary battery, but is preferably a secondary battery. The type of secondary battery to which the exterior material for an electric storage device of the present disclosure is applied is not particularly limited, and examples thereof include lithium ion batteries, lithium ion polymer batteries, all-solid-state batteries, lead-acid batteries, nickel-hydrogen batteries, nickel-cadmium batteries, nickel-iron batteries, nickel-zinc batteries, silver oxide-zinc batteries, metal-air batteries, polyvalent cation batteries, condensers, and capacitors. Among these secondary batteries, examples of suitable applications of the exterior material for an electric storage device of the present disclosure include lithium ion batteries and lithium ion polymer batteries. EXAMPLES
[0153] The present disclosure will be described in detail below with reference to examples and comparative examples. However, the present disclosure is not limited to the examples.
[0154] <Manufacture of exterior materials for power storage devices> Example 1 and Comparative Example 1 As the substrate layer, a polyethylene terephthalate (PET) film (thickness 12 μm) and an oriented nylon (ONy) film (thickness 15 μm) were prepared, and a two-liquid type urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to the PET film (3 μm) to adhere to the ONy film. In addition, an aluminum foil (JIS H4160:1994 A8021H-O (thickness 40 μm)) was prepared as the barrier layer. Next, a two-liquid type urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum foil to form an adhesive layer (thickness 3 μm) on the barrier layer. Next, the adhesive layer on the barrier layer and the substrate layer (ONy film side) were laminated by the dry lamination method, and then aging treatment was performed to produce a substrate layer / adhesive layer / barrier layer laminate. Both sides of the aluminum foil were subjected to chemical conversion treatment. The chemical conversion treatment of aluminum foil is carried out using a treatment solution consisting of phenolic resin, chromium fluoride compound, and phosphoric acid, with a coating amount of chromium of 10 mg / m 2 (dry weight) was applied to both sides of an aluminum foil by roll coating, and then baked.
[0155] Next, on the barrier layer of each laminate obtained above, maleic anhydride modified polypropylene as an adhesive layer (thickness 20 μm), random polypropylene as a second heat-sealable resin layer (thickness 50 μm), and random polypropylene as a first heat-sealable resin layer (thickness 10 μm) were co-extruded to laminate the adhesive layer / second heat-sealable resin layer / first heat-sealable resin layer on the barrier layer, and a packaging material for a storage device was obtained in which the base layer (thickness 30 μm including adhesive) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (20 μm) / second heat-sealable resin layer (50 μm) / first heat-sealable resin layer (10 μm) were laminated in this order. The first heat-sealable resin layers of Example 1 and Comparative Example 1 each have the logarithmic decrement ΔE at 140 ° C. (value measured using a rigid pendulum type physical property tester) shown in Table 1.
[0156] Example 2 and Comparative Example 2 As the substrate layer, a polyethylene terephthalate (PET) film (thickness 12 μm) and an oriented nylon (ONy) film (thickness 15 μm) were prepared, and a two-liquid type urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to the PET film (3 μm) to adhere to the ONy film. In addition, an aluminum foil (JIS H4160:1994 A8021H-O (thickness 40 μm)) was prepared as the barrier layer. Next, a two-liquid type urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum foil to form an adhesive layer (thickness 3 μm) on the barrier layer. Next, the adhesive layer on the barrier layer and the substrate layer (ONy film side) were laminated by the dry lamination method, and then aging treatment was performed to produce a substrate layer / adhesive layer / barrier layer laminate. Both sides of the aluminum foil were subjected to chemical conversion treatment. The chemical conversion treatment of aluminum foil is carried out using a treatment solution consisting of phenolic resin, chromium fluoride compound, and phosphoric acid, with a coating amount of chromium of 10 mg / m 2 (dry weight) was applied to both sides of an aluminum foil by roll coating, and then baked.
[0157] Next, on the barrier layer of each laminate obtained above, maleic anhydride modified polypropylene as an adhesive layer (thickness 40 μm) and random polypropylene as a first heat-sealable resin layer (thickness 40 μm) were co-extruded to laminate the adhesive layer / first heat-sealable resin layer on the barrier layer, thereby obtaining an exterior material for a storage battery device in which the base layer (thickness 30 μm including adhesive) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (40 μm) / first heat-sealable resin layer (40 μm) were laminated in this order. The first heat-sealable resin layers of Example 2 and Comparative Example 2 each have the logarithmic decrement ΔE at 140° C. (value measured using a rigid pendulum type physical property tester) shown in Table 1.
[0158] Example 3 Except for using a polyethylene terephthalate (PET) film (thickness 25 μm) instead of a laminate of a polyethylene terephthalate (PET) film (thickness 12 μm) and an oriented nylon (ONy) film (thickness 15 μm) as the base material layer, an exterior material for an electricity storage device was obtained in the same manner as in Example 1, in which the base material layer (thickness 25 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (20 μm) / second heat-sealable resin layer (50 μm) / first heat-sealable resin layer (10 μm) were laminated in that order.
[0159] Example 4 An exterior material for a power storage device was obtained in the same manner as in Example 1, except that a stretched nylon (ONy) film (thickness 25 μm) was used as the base material layer instead of a laminate of a polyethylene terephthalate (PET) film (thickness 12 μm) and a stretched nylon (ONy) film (thickness 15 μm). The exterior material was laminated in the following order: base material layer (thickness 25 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (20 μm) / second heat-sealable resin layer (50 μm) / first heat-sealable resin layer (10 μm).
[0160] <Measurement of logarithmic decrement ΔE of first heat-sealable resin layer> Each of the electrical storage device exterior materials obtained above was cut into a rectangle with a width (TD: transverse direction) of 15 mm and a length (MD: machine direction) of 45 mm to prepare a test sample (electricity storage device exterior material 10). The MD of the electrical storage device exterior material corresponds to the rolling direction (RD) of the aluminum alloy foil, and the TD of the electrical storage device exterior material corresponds to the TD of the aluminum alloy foil, and the rolling direction (RD) of the aluminum alloy foil can be determined from the rolling grain. When the MD of the electrical storage device exterior material cannot be determined from the rolling grain of the aluminum alloy foil, it can be determined by the following method. As a method for confirming the MD of the electrical storage device exterior material, the cross section of the heat-sealable resin layer of the electrical storage device exterior material is observed with an electron microscope to confirm the sea-island structure, and the direction parallel to the cross section where the average diameter of the island shape in the direction perpendicular to the thickness direction of the heat-sealable resin layer is maximum can be determined as the MD. Specifically, the sea-island structure is confirmed by observing the cross section in the longitudinal direction of the heat-sealable resin layer and each cross section (a total of 10 cross sections) at an angle of 10 degrees from the direction parallel to the cross section in the longitudinal direction to the direction perpendicular to the cross section in the longitudinal direction. Next, the shape of each island is observed in each cross section. The straight-line distance connecting the leftmost end in the direction perpendicular to the thickness direction of the heat-sealable resin layer to the rightmost end in the perpendicular direction is defined as the diameter y of each island shape. The average of the diameters y of the top 20 island shapes in order of the largest diameter y in each cross section is calculated. The direction parallel to the cross section with the largest average diameter y of the island shapes is determined as MD. A schematic diagram for explaining the method of measuring the logarithmic decrement ΔE by rigid pendulum measurement is shown in FIG. 6. A rigid pendulum type physical property tester (model number: RPT-3000W manufactured by A&D Co., Ltd.) was used, with FRB-100 for the frame of the pendulum 30, RBP-060 for the cylindrical cylinder edge 30a of the edge portion, CHB-100 for the cooling block 31, a vibration displacement detector 32, and a weight 33, and the initial amplitude was set to 0.3 degrees. The test sample was placed on the cooling block 31 with the measurement surface (first heat-fusible resin layer) facing upward, and the cylindrical cylinder edge 30a with the pendulum 30 was installed on the measurement surface so that the axial direction of the cylindrical cylinder edge 30a with the pendulum 30 was perpendicular to the MD direction of the test sample.In addition, in order to prevent the test sample from floating or warping during the measurement, tape was attached to a portion of the test sample that would not affect the measurement results, and the test sample was fixed on the cooling block 31. The cylindrical cylinder edge 30a was brought into contact with the surface of the first heat-sealable resin layer. Next, the logarithmic attenuation rate ΔE of the first heat-sealable resin layer was measured in the temperature range of 30°C to 200°C at a temperature rise rate of 3°C / min using the cooling block 31. The logarithmic attenuation rate ΔE was measured when the surface temperature of the first heat-sealable resin layer of the test sample (exterior material 10 for power storage devices) reached 140°C. (The test sample that had been measured once was not used, and the average value of three measurements (N=3) using newly cut samples was used.) For the first heat-sealable resin layer, each exterior material for power storage devices obtained above was immersed in 15% hydrochloric acid to dissolve the base layer and aluminum foil, and the test sample that was left with only the adhesive layer and the heat-sealable resin layer was thoroughly dried to measure the logarithmic attenuation rate ΔE. The logarithmic decrement ΔE at 140° C. is shown in Table 1. The logarithmic decrement ΔE is calculated by the following formula. ΔE=[ln(A1 / A2)+ln(A2 / A3)+...+ln(An / An+1)] / n A: Amplitude n: wave number
[0161] In addition, the logarithmic decrement ΔE at 80° C. was measured in the same manner as in <Measurement of logarithmic decrement ΔE of first heat-sealable resin layer>, except that the logarithmic decrement ΔE was measured when the surface temperature of the first heat-sealable resin layer was 80° C. The results are shown in Table 1.
[0162] <Measurement of remaining ratio of thickness of first heat-sealable resin layer> Each of the obtained exterior materials for electric storage devices was cut to a length of 150 mm and a width of 60 mm to prepare a test sample (exterior material for electric storage devices 10). Next, the first heat-sealable resin layers of the test samples prepared from the same exterior material for electric storage devices were placed opposite each other. Next, in this state, a metal plate having a width of 7 mm was used to heat and pressurize both sides of the test sample in the stacking direction under conditions of a temperature of 190° C., each surface pressure (MPa) listed in Table 1, and a time of 3 seconds to heat-seal the first heat-sealable resin layer. Next, the heat-sealed portion of the test sample was cut in the stacking direction using a microtome, and the thicknesses of the two first heat-sealable resin layers that were heat-sealed to each other were measured for the exposed cross section. The test sample before heat-sealing was also cut in the stacking direction using a microtome in the same manner, and the thicknesses of the two first heat-sealable resin layers were measured for the exposed cross section. The ratio of the total thickness of the two first heat-sealable resin layers after heat fusion to the total thickness of the two first heat-sealable resin layers before heat fusion was calculated, and the remaining ratio (%) of the total thickness of the two first heat-sealable resin layers was measured. The results are shown in Table 1.
[0163] <Observation of the cross-sectional structure of the heat-sealed part> Heat and pressure were applied to each of the exterior materials for power storage devices under conditions of a width of 7 mm, a temperature of 190°C, a pressure of 0.5 MPa, and a duration of 3 seconds to thermally fuse the heat-sealable resin layers together to form the heat-sealed portion. Next, the heat-sealed portion was cut in the thickness direction using a microtome, and the resulting cross section was observed under a microscope. The microscope used was a VK-9710 manufactured by Keyence Corporation. For reference, micrographs of the cross sections of Examples 1 and 2 and Comparative Examples 1 and 2 are shown in FIG. 7 (Example 1), FIG. 8 (Example 2), FIG. 9 (Comparative Example 1), and FIG. 10 (Comparative Example 2), respectively. Note that the micrographs in FIG. 7 to FIG. 10 show the positions of the base layer 1, adhesive layer 2, barrier layer 3, adhesive layer 5, first heat-sealable resin layer 41, and second heat-sealable resin layer 42, respectively.
[0164] Based on the micrographs, the cross-sectional structure of the heat-sealed portion was evaluated according to the following criteria. The results are shown in Table 1. The following evaluations A and B indicate that the collapse of the first heat-sealable resin layer during heat fusion was effectively suppressed. A: In the heat-sealed portion, the heat-sealable resin layer does not protrude inward (toward the space in which the exterior packaging material for an electricity storage device is housed). B: In the heat-sealed portion, the heat-sealable resin layer slightly protrudes inward (toward the space in which the exterior material for an electricity storage device is housed). C: In the heat-sealed portion, the heat-sealable resin layer significantly protrudes inward (toward the space in which the exterior material for an electricity storage device is housed).
[0165] [Table 1]
[0166] In Table 1, DL indicates the adhesive that bonds the polyethylene terephthalate film and the stretched nylon film. In addition, in the second heat-sealable resin layer / first heat-sealable resin layer, the notation "-" indicates that the second heat-sealable resin layer is not provided.
[0167] As is clear from the results shown in Table 1, the exterior packaging material for an energy storage device of Example 1-4 has a first heat-sealable resin layer constituting the surface having a logarithmic decrement ΔE of 0.20 or less at 140°C, and it is found that crushing when the first heat-sealable resin layer is heat-sealed is effectively suppressed.
[0168] As described above, the present disclosure provides the following aspects of the invention. Item 1. The laminate includes at least a base layer, a barrier layer, and a heat-sealable resin layer in this order. The thermally adhesive resin layer is configured as a single layer or multiple layers, An exterior material for an electricity storage device, wherein among the heat-sealable resin layers, a first heat-sealable resin layer constituting a surface of the laminate has a logarithmic decrement ΔE of 0.20 or less at 140°C in a rigid pendulum measurement. Item 2. The packaging material for an electricity storage device according to Item 1, wherein the first heat-sealable resin layer has a thickness of 5 μm or more and 25 μm or less. Item 3. The exterior packaging material for an electricity storage device according to Item 1 or 2, wherein after the first heat-sealable resin layers of the laminate are placed opposite each other and heated and pressurized in the lamination direction under conditions of a temperature of 190° C., a surface pressure of 2.0 MPa, and a time of 3 seconds, a remaining ratio of a total thickness of the two opposed first heat-sealable resin layers is 30% or more. Item 4. The packaging material for an electricity storage device according to any one of Items 1 to 3, wherein a resin constituting the first thermally adhesive resin layer contains a polyolefin skeleton. Item 5. The packaging material for an electricity storage device according to any one of Items 1 to 4, further comprising an adhesive layer between the barrier layer and the heat-sealable resin layer. Item 6. The packaging material for an electricity storage device according to Item 5, wherein a total thickness of the adhesive layer and the heat-sealable resin layer is 50 μm or more. Item 7. The packaging material for an electricity storage device according to Item 5 or 6, wherein the adhesive layer has a thickness equal to or greater than a thickness of the first thermally adhesive resin layer. Item 8. The thermally adhesive resin layer includes, in order from the surface side of the laminate, the first thermally adhesive resin layer and the second thermally adhesive resin layer, Item 8. The exterior packaging material for an electricity storage device according to any one of items 5 to 7, wherein the second heat-sealable resin layer has a thickness equal to or greater than a thickness of the adhesive layer. Item 9. The packaging material for an electricity storage device according to any one of Items 5 to 8, wherein a thickness of the second heat-sealable resin layer is greater than a thickness of the first heat-sealable resin layer. Item 10. The exterior packaging material for an electricity storage device according to any one of Items 5 to 9, wherein the adhesive layer has a thickness of 50 μm or less. Item 11. The packaging material for an electricity storage device according to any one of Items 1 to 10, wherein a lubricant is present on a surface of the first heat-sealable resin layer. Item 12. The method includes a step of laminating at least a base layer, a barrier layer, and a heat-sealable resin layer in this order to obtain a laminate, The thermally adhesive resin layer is configured as a single layer or multiple layers, A method for producing an exterior material for an electricity storage device, wherein, among the heat-sealable resin layers, a first heat-sealable resin layer constituting a surface of the laminate has a logarithmic decrement ΔE of 0.20 or less at 140°C in a rigid pendulum measurement. Item 13. An electricity storage device, comprising an electricity storage device element including at least a positive electrode, a negative electrode, and an electrolyte, housed in a package formed from the exterior material for an electricity storage device according to any one of Items 1 to 11. [Explanation of symbols]
[0169] 1 Base material layer 2 Adhesive layer 3. Barrier layer 4 Heat-fusible resin layer 5 Adhesive layer 6 Surface coating layer 10. Exterior materials for energy storage devices 41 First heat-fusible resin layer 42 Second heat-fusible resin layer
Claims
1. The laminate includes at least a base layer, a barrier layer, an adhesive layer, and a heat-sealable resin layer in this order. The thermally adhesive resin layer includes a first thermally adhesive resin layer and a second thermally adhesive resin layer, Among the heat-fusible resin layers, a first heat-fusible resin layer constituting a surface of the laminate has a logarithmic decrement ΔE of 0.20 or less at 140° C. in a rigid pendulum measurement; In measuring the logarithmic decrement ΔE, a rigid pendulum physical test is performed on the first heat-sealable resin layer using a commercially available rigid pendulum physical tester under the conditions of a cylindrical cylinder edge as an edge portion pressed against the first heat-sealable resin layer, an initial amplitude of 0.3 degrees, a temperature range of 30° C. to 200° C., and a temperature rise rate of 3° C. / min. For the first heat-fusible resin layer for which the logarithmic decrement ΔE is measured, the laminate is immersed in 15% hydrochloric acid to dissolve the base material layer and the barrier layer, and the laminate of the adhesive layer and the heat-fusible resin layer is thoroughly dried to obtain a measurement target. The first thermally adhesive resin layer is formed of random polypropylene, the second thermal adhesive resin layer is formed of a resin containing a polyolefin skeleton, The resin forming the adhesive layer contains a polyolefin skeleton, The thickness ratio of the first heat-sealable resin layer to the thickness of the adhesive layer is 0.5 or more and 3.0 or less, and the thickness ratio of the second heat-sealable resin layer is 1.5 or more and 6.0 or less, with respect to the thickness of the first heat-sealable resin layer being 1.0; The thickness of the adhesive layer is equal to or greater than the thickness of the first thermal adhesive resin layer, The second heat-sealable resin layer has a thickness equal to or greater than a thickness of the adhesive layer.
2. The packaging material for an electricity storage device according to claim 1 , wherein the first thermally adhesive resin layer has a thickness of 5 μm or more and 25 μm or less.
3. 3. The exterior material for an electricity storage device according to claim 1 or 2, wherein after the first heat-sealable resin layers of the laminate are placed opposite each other and heated and pressurized in the lamination direction under conditions of a temperature of 190° C., a surface pressure of 2.0 MPa, and a time of 3 seconds, a remaining ratio of a total thickness of the two opposed first heat-sealable resin layers is 30% or more.
4. The base layer includes a laminate of a polyester film and a polyamide film, a laminate of a polyester film and a polyester film, or a laminate of a polyamide film and a polyamide film. The exterior material for a storage battery device according to any one of claims 1 to 3.
5. The packaging material for an electricity storage device according to any one of claims 1 to 4, wherein two or more types of lubricants are present on at least one of a surface and an interior of the heat-fusible resin layer.
6. The electrical storage device packaging material according to any one of claims 1 to 5, wherein the barrier layer includes at least one of an aluminum alloy foil and a stainless steel foil.
7. The exterior material for an electricity storage device according to any one of claims 1 to 6, further comprising a surface coating layer on the opposite side of the base material layer to the barrier layer side.
8. The exterior material for an electricity storage device according to any one of claims 1 to 7, wherein the base material layer has a thickness of more than 35 µm and not more than 50 µm.
9. The exterior material for an electricity storage device according to any one of claims 1 to 8, wherein the barrier layer has a thickness of more than 50 µm and not more than 85 µm.
10. The exterior material for an electricity storage device according to any one of claims 1 to 8, wherein the barrier layer has a thickness of more than 85 µm and not more than 200 µm.
11. The method includes a step of laminating at least a base layer, a barrier layer, an adhesive layer, and a thermally adhesive resin layer in this order to obtain a laminate, The thermally adhesive resin layer includes a first thermally adhesive resin layer and a second thermally adhesive resin layer, Among the heat-fusible resin layers, a first heat-fusible resin layer constituting a surface of the laminate has a logarithmic decrement ΔE of 0.20 or less at 140° C. in a rigid pendulum measurement; In measuring the logarithmic decrement ΔE, a rigid pendulum physical test is performed on the first heat-sealable resin layer using a commercially available rigid pendulum physical tester under the conditions of a cylindrical cylinder edge as an edge portion pressed against the first heat-sealable resin layer, an initial amplitude of 0.3 degrees, a temperature range of 30° C. to 200° C., and a temperature rise rate of 3° C. / min. For the first heat-fusible resin layer for which the logarithmic decrement ΔE is measured, the laminate is immersed in 15% hydrochloric acid to dissolve the base material layer and the barrier layer, and the laminate of the adhesive layer and the heat-fusible resin layer is thoroughly dried to obtain a measurement target. The first thermally adhesive resin layer is formed of random polypropylene, the second thermal adhesive resin layer is formed of a resin containing a polyolefin skeleton, The resin forming the adhesive layer contains a polyolefin skeleton, The thickness ratio of the first heat-sealable resin layer to the thickness of the adhesive layer is 0.5 or more and 3.0 or less, and the thickness ratio of the second heat-sealable resin layer is 1.5 or more and 6.0 or less, with respect to the thickness of the first heat-sealable resin layer being 1.0; The thickness of the adhesive layer is equal to or greater than the thickness of the first thermal adhesive resin layer, a thickness of the second heat-sealable resin layer is equal to or greater than a thickness of the adhesive layer.
12. an adhesive layer is provided between the barrier layer and the thermal adhesive resin layer, 12. The method for producing an exterior material for an electricity storage device according to claim 11, wherein the adhesive layer and the heat-sealable resin layer are formed by a co-extrusion lamination method, a tandem lamination method, a thermal lamination method, a sandwich lamination method, or a method of solution-coating an adhesive for forming the adhesive layer on the barrier layer and laminating the heat-sealable resin layer, which has been formed in advance into a sheet shape, on the adhesive layer.
Citation Information
Patent Citations
Sheath material for lithium cell
JP2006134692A
Laminate film for battery outer packaging and method for producing the same
JP2014026778A
Battery packaging material
JP2015035325A
Sheath material for secondary battery
JP2017004765A
Layered package material, outer package material for battery, and the battery
JP2008287971A